Zinc-coated steel sheets, components and their manufacturing methods

A high-strength galvanized steel sheet with controlled steel structure and hydrogen trapping carbides addresses hydrogen embrittlement issues, enhancing bendability, stretch flangeability, and yield ratio, suitable for automotive use.

JP7613635B2Active Publication Date: 2025-01-15JFE STEEL CORP
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2024512882
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-03-31
Filing Date
2023-03-31
Publication Date
2025-01-15
Estimated Expiration
2043-03-31

AI Technical Summary

Technical Problem

Existing high-strength hot-dip galvanized steel sheets face issues with hydrogen embrittlement, leading to deterioration in bendability, stretch flangeability, and cracking in spot welds, while existing solutions do not adequately address hydrogen embrittlement resistance during manufacturing.

Method used

A galvanized steel sheet with a specific steel structure comprising less than 65% ferrite, 25% or more of total martensite and bainite, 3% to 10% retained austenite, and 70% or more of tempered martensite with carbides of 50 nm to 200 nm, along with controlled hydrogen trapping through carbides, achieving a tensile strength of 780 MPa to 1180 MPa, yield ratio of 0.60 or more, and low diffusible hydrogen content.

Benefits of technology

The solution provides a galvanized steel sheet with enhanced bendability, stretch flangeability, and hydrogen embrittlement resistance, ensuring high yield ratio and reduced risk of cracking in spot welds, suitable for automotive applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007613635000006
    Figure 0007613635000006
  • Figure 0007613635000007
    Figure 0007613635000007
  • Figure 0007613635000001
    Figure 0007613635000001
Patent Text Reader

Abstract

Provided are technical features of a galvanized steel sheet that has a high yield ratio, excellent bending property and stretch flangeability, excellent hydrogen embrittlement resistance, and a TS that is more than or equal to 780 MPa and less than 1180 MPa. The galvanized steel sheet comprises: a steel structure in which, in area ratio, ferrite is less than 65%, a total of martensite and bainite is more than or equal to 25%, residual austenite is 3-10%, and 70% or more of all martensite in the steel structure at plate thicknesses 1 / 8 to 3 / 8 of a base steel sheet is tempered martensite including a carbide with an average particle size of 50-200 nm; and a galvanized layer formed on the base steel sheet. In the galvanized steel sheet, TS is more than or equal to 780 MPa and less than 1180 MPa, a yield ratio is more than or equal to 0.60, and the amount of diffusible hydrogen is less than or equal to 0.45 mass ppm.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a high-strength galvanized steel sheet having excellent workability, a member made of the high-strength galvanized steel sheet, and a method for producing the same. The galvanized steel sheet of the present invention is preferably usable mainly as a steel sheet for automobiles. [Background technology]

[0002] In recent years, from the viewpoint of global environmental conservation, there has been a strong demand for improving fuel efficiency to reduce CO2 emissions from automobiles. Accordingly, there has been an active movement to reduce the weight of automobile bodies by thinning the body parts, and the need for high strength steel sheets, which are materials for automobile body parts. In particular, from the viewpoint of ensuring collision safety of automobiles, steel sheet materials used around the cabin are required to have not only high tensile strength but also high yield strength. In addition, it is necessary to have press formability so that the freedom of part shape is not lost due to high strength. Furthermore, if corrosion progresses during use as an automobile part, the original material strength may not be exhibited in the event of a collision, so the application of hot-dip galvanized steel sheets, which have excellent corrosion resistance, is expanding.

[0003] On the other hand, increasing the strength of steel sheets is accompanied by concerns about the occurrence of hydrogen embrittlement. Hydrogen embrittlement of high-strength steel sheets can be caused not only by hydrogen that invades from the outside due to corrosion during use, but also by hydrogen that invades during the manufacturing process. In particular, in the case of hot-dip galvanized steel sheets, a general method is to manufacture the steel sheets by continuously performing a series of processes from annealing to hot-dip galvanizing in a hydrogen-containing atmosphere in order to suppress reduction and oxidation of the steel sheets. For this reason, the galvanized layer is formed in a state in which hydrogen that invaded the steel from the atmosphere remains. Hydrogen diffusion during galvanization is very slow and acts as a barrier against the external release of diffusible hydrogen in the steel, so that diffusible hydrogen remains and hydrogen embrittlement during processing may promote cracking, and there is a risk of causing deterioration of local ductility, especially bendability and stretch flangeability. Therefore, it is important to establish a hot-dip galvanized steel sheet with excellent hydrogen embrittlement resistance in which hydrogen in the steel is sufficiently reduced, and a manufacturing method thereof.

[0004] Regarding the problems related to the workability and hydrogen embrittlement resistance of high-strength hot-dip galvanized steel sheets, for example, Patent Document 1 discloses a high-strength hot-dip galvanized steel sheet with excellent bendability and a manufacturing method thereof. Also, Patent Document 2 discloses a high-strength steel sheet of TS900 MPa or more with excellent ductility and delayed fracture resistance, a manufacturing method of a high-strength cold-rolled steel sheet, and a manufacturing method of a high-strength galvanized steel sheet. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] International Publication No. 2016 / 113788 [Patent Document 2] JP 2011-111671 A Summary of the Invention [Problem to be solved by the invention]

[0006] However, while Patent Document 1 describes the improvement of bendability by refining martensite grains, it does not disclose a method for improving hydrogen embrittlement resistance. Also, Patent Document 2 describes the compatibility of ductility and hydrogen embrittlement resistance, but deals with hydrogen embrittlement resistance after processing, and does not describe the improvement of hydrogen embrittlement resistance caused by hydrogen that enters the steel during manufacturing. It is believed that the manufacturing methods disclosed in these patent documents result in a large amount of hydrogen remaining in the steel, which poses a risk of hydrogen embrittlement occurring during the processing, such as deterioration of bendability and stretch flangeability, and cracking in nuggets of spot welds.

[0007] The present invention has been made in view of the above circumstances, and provides a galvanized steel sheet, a member, and a manufacturing method thereof, which are suitable for automotive applications and have a high yield ratio (YR), excellent bendability and stretch flangeability, and excellent hydrogen embrittlement resistance, and a tensile strength (TS) of 780 MPa or more and less than 1180 MPa.

[0008] In this case, a high yield ratio means that a JIS No. 5 tensile test piece (JIS Z2201) is taken perpendicular to the rolling direction and the strain rate is increased to 10 -3 This indicates that the YR is 0.60 or more when a tensile test is conducted in accordance with the provisions of JIS Z2241 (2011) for Yield Strength / s.

[0009] Tensile strength (TS) was measured by taking JIS No. 5 tensile test pieces (JIS Z2201) perpendicular to the rolling direction and increasing the strain rate to 10 -3 This refers to the tensile strength obtained by conducting a tensile test in accordance with the provisions of JIS Z2241 (2011) at 100 / s.

[0010] Excellent bendability refers to a condition in which a rectangular test piece of 35 mm x 100 mm is taken from a galvanized steel sheet so that the direction parallel to the rolling direction is the bending test axis, and a 90-degree V-bend test is performed with various bending radii at a stroke speed of 50 mm / s, a pressing load of 10 ton, and a pressing hold time of 5 seconds. The ridgeline at the bent apex of the test piece is observed with a 10x magnifying glass, and R / t, which is the minimum bending radius R (mm) at which no cracks of 0.5 mm or more in length were observed, is calculated by dividing the value by the sheet thickness (mm), and the result satisfies either (A) or (B) below. (A) TS: 780MPa or more but less than 980MPa and R / t: 4.5 or less (B) TS: 980MPa or more but less than 1180MPa and R / t: 5.0 or less

[0011] Excellent stretch flangeability refers to a test piece of 100 mm × 100 mm taken from a galvanized steel sheet, a hole of 10 mm diameter with a clearance of 12.5% ​​is formed in the center of the test piece by punching, and then a die with an inner diameter of 75 mm is used to apply a wrinkle suppression force of 9 tons (88.26 kN) around the hole, and a conical punch with an apex angle of 60° is pressed into the hole to expand it, and the diameter of the hole when a crack occurs is measured, and the limiting hole expansion ratio λ (%) calculated from the following formula (1) is 35% or more. λ(%)={(D f -D0) / D0}×100...Equation (1) D f: Diameter of hole when crack occurs (mm) D0: Hole diameter before hole expansion (mm)

[0012] "Excellent resistance to hydrogen embrittlement" means that when spot welding is performed using the following method, the cracks in the resulting nugget are 100 μm or less. (1) A 30 mm x 100 mm test piece was taken from a galvanized steel plate. A 2 mm thick spacer was placed on both ends of the test piece, and the center between the spacers was spot welded to prepare a welded test piece. (2) For spot welding, an inverter DC resistance spot welding machine is used, and the electrode is a dome-shaped chromium copper electrode with a tip diameter of 6 mm. The pressure is 380 kgf, the current flow time is 16 cycles / 50 Hz, and the holding time is 5 cycles / 50 Hz. (3) The welding current value is adjusted so as to form a nugget diameter according to the plate thickness. The nugget diameter shall satisfy the following formula (2). 3.0×t 1 / 2 < nugget diameter < 3.5×t 1 / 2 ...Equation (2) In formula (2), t is the plate thickness (mm). (4) After leaving the spot welded for 24 hours, the spacer portion is cut off and the cross section of the nugget is observed. [Means for solving the problem]

[0013] The present inventors have conducted extensive research to solve the above problems, and as a result, have found that it is possible to reduce diffusible hydrogen in steel by optimizing the steel sheet structure and appropriately controlling the precipitation morphology of carbides in the steel and utilizing them as hydrogen trapping sites, thereby making it possible to obtain a high-strength galvanized steel sheet that has a high yield ratio, excellent bendability, and a low risk of cracking in the nugget of a spot weld.

[0014] The present invention was made based on these findings, and the gist of the present invention is as follows. [1] A galvanized steel sheet having a base steel sheet and a galvanized layer formed on the base steel sheet, The base steel sheet is In terms of area ratio, Ferrite: less than 65% The sum of martensite and bainite: 25% or more, Retained austenite: A steel structure having 3% to 10%. In terms of area ratio, 70% or more of all martensite in the steel structure in 1 / 8 to 3 / 8 of the sheet thickness of the base steel sheet is tempered martensite having carbides with an average grain size of 50 nm or more and 200 nm or less, The tensile strength is 780 MPa or more and less than 1180 MPa, The yield ratio is 0.60 or more, The zinc-plated steel sheet has an integrated amount of hydrogen released when the base steel sheet is heated from room temperature to 200°C of 0.45 mass ppm or less. [2] The steel composition of the base steel sheet is, in mass%, C: 0.080% or more and 0.300% or less, Si: 0.20% or more and 2.00% or less, Mn: 1.00% or more and 4.00% or less, P: 0.10% or less, S: 0.0200% or less, Al: 0.003% or more and 0.100% or less, N: Contains 0.0100% or less, The zinc-plated steel sheet according to [1] above, wherein the balance consists of Fe and unavoidable impurities. [3] The steel composition further comprises, in mass%, B: 0.0100% or less, Ti: 0.200% or less, Nb: 0.200% or less, Sb: 0.200% or less, Sn: 0.200% or less, V: 0.100% or less, Cu: 2.00% or less, Cr: 2.00% or less, Ni: 2.00% or less, Mo: 1.00% or less Ta: 0.100% or less, W: 0.500% or less, Zr: 0.020% or less, Ca: 0.0200% or less, Mg: 0.0200% or less, Zn: 0.020% or less, Co: 0.020% or less, Ce: 0.0200% or less, Se: 0.0200% or less, Te: 0.0200% or less, Ge: 0.0200% or less, As: 0.0200% or less, Sr: 0.0200% or less, Cs: 0.0200% or less, Hf: 0.0200% or less, Pb: 0.0200% or less, Bi: 0.0200% or less and REM (excluding Ce): At least one selected from below 0.0200% The zinc-plated steel sheet according to [2] above, which contains [4] The galvanized steel sheet according to any one of [1] to [3], wherein the base steel sheet has a soft surface layer in a region of 200 μm or less from the surface of the base steel sheet in the sheet thickness direction, the soft surface layer having a Vickers hardness of 85% or less of the Vickers hardness at 1 / 4 of the sheet thickness. [5] When the nano hardness is measured at 300 points or more in a 50 μm × 50 μm area on the sheet surface at a 1 / 4 position and a 1 / 2 position of the sheet thickness direction depth of the soft surface layer from the surface of the base steel sheet, The ratio of the number of measurements of nano hardness of the sheet surface at a position of 1 / 4 of the sheet thickness direction depth of the soft surface layer from the surface of the base steel sheet, which is 7.0 GPa or more, to the total number of measurements is 0.10 or less, Furthermore, the standard deviation σ of the nanohardness of the sheet surface at a position of 1 / 4 of the sheet thickness direction depth of the soft surface layer from the surface of the base steel sheet is 1.8 GPa or less, The galvanized steel sheet according to [4], further comprising a standard deviation σ of nano-hardness of the sheet surface at a position half the depth in the sheet thickness direction of the soft surface layer from the surface of the base steel sheet being 2.2 GPa or less. [6] The zinc-plated steel sheet according to any one of [1] to [5], having a metal plating layer formed between the base steel sheet and the zinc plating layer on one or both sides of the zinc-plated steel sheet. [7] The galvanized steel sheet according to any one of the above [1] to [6], wherein the galvanized layer is a galvannealed layer. [8] The galvanized steel sheet according to any one of [1] to [7], wherein when the base steel sheet is heated from room temperature to 600°C, the integrated amount of hydrogen released in a temperature range of 350 to 600°C is 0.05 ppm by mass or more. [9] A member made using the zinc-plated steel sheet according to any one of [1] to [8] above.

[10] A hot rolling process in which a slab having the steel composition described in [2] or [3] is heated to a temperature range of 1100 to 1350 ° C, hot rolled at a finish rolling end temperature of 800 to 950 ° C, and coiled at a coiling temperature of 650 ° C or less; A reduction process in which the steel sheet after the hot rolling process is held at 700° C. or higher in a reducing atmosphere having a hydrogen concentration of 8% by volume or more and 30% by volume or less for 20 s or more; a soaking step of holding the steel sheet after the reduction step in a soaking atmosphere having a hydrogen concentration of 0.2 volume% to 8 volume% at 750°C or higher for 20 s to 300 s; A first cooling step of cooling the steel sheet after the soaking step; a galvanizing step of forming a galvanized layer on the surface of the steel sheet after the first cooling step; a second cooling step in which the steel sheet after the galvanizing step is cooled from a temperature range of 350 to 450°C to (Ms point - 100°C) at an average cooling rate of 20°C / s or less and is retained in a temperature range of 100 to 350°C for 5 seconds or more to a cooling stop temperature of 100 to 300°C; A reheating process in which the steel sheet after the second cooling process is held in a temperature range of from the cooling stop temperature to 450 ° C. for 5 to 600 s; A method for producing a galvanized steel sheet, comprising:

[11] The method for producing a zinc-plated steel sheet according to

[10] , wherein after the zinc plating step, the zinc plating layer is formed on the surface of the steel sheet, and then an alloying treatment is further performed.

[12] The method for producing a galvanized steel sheet according to

[10] or

[11] , further comprising a cold rolling step of cold rolling at a reduction ratio of 20% or more after the hot rolling step and before the reducing step.

[13] The method for producing a galvanized steel sheet according to any one of

[10] to

[12] , wherein in the first cooling step, the steel sheet after the soaking step is cooled from 600 to 900°C to 150 to 500°C at an average cooling rate of 20°C / s or less in an atmosphere with a hydrogen concentration of 0.5 vol% or more and 30 vol% or less and a dew point of 0°C or less.

[14] The method for producing a galvanized steel sheet according to any one of

[10] to

[13] , wherein in the second cooling step, the average cooling rate from the temperature range of 350 to 450°C to (Ms point - 100°C) is 10°C / s or less, and the steel is retained in the temperature range of 100 to 350°C for 10 seconds or more to cool to a cooling stop temperature of 100 to 300°C.

[15] The method for producing a galvanized steel sheet according to any one of

[10] to

[14] , wherein the soaking atmosphere in the soaking step has a dew point of -30°C or higher.

[16] The method for producing a galvanized steel sheet according to any one of the items

[10] to

[15] , further comprising a pre-plating step of applying metal plating to one or both sides of the steel sheet after the hot rolling step and before the reducing step to form a metal plating layer.

[17] The method for producing a galvanized steel sheet according to any one of the items

[10] to

[16] , further comprising an oxidation step of heating the steel sheet after the hot rolling step and before the reduction step to 600°C or higher in an oxidizing atmosphere containing an oxygen concentration of 1000 ppm by volume or more and 30000 ppm by volume or less.

[18] A method for producing a component, comprising the step of subjecting the zinc-plated steel sheet according to any one of [1] to [8] above to at least one of forming and joining to produce a component. Effect of the Invention

[0015] The galvanized steel sheet provided by the present invention has a tensile strength of 780 MPa or more and less than 1,180 MPa, a yield ratio of 0.60 or more, and is excellent in bendability, stretch flangeability and resistance to hydrogen embrittlement. Furthermore, the member provided by the present invention has a tensile strength of 780 MPa or more and less than 1180 MPa, a yield ratio of 0.60 or more, and is excellent in bendability, stretch flangeability, and resistance to hydrogen embrittlement. [Brief description of the drawings]

[0016] [Figure 1] FIG. 1 is a diagram for explaining (a) the primary bending process and (b) the secondary bending process in the U-bending+contact bending test and the V-bending+orthogonal VDA bending test of the examples. [Diagram 2] FIG. 2 is (a) a front view and (b) a perspective view of a test member produced for the axial crush test of the embodiment, in which a hat-shaped member and a steel plate are spot-welded, and (c) a schematic diagram for explaining the axial crush test. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] The present invention will be described in detail below.

[0018] <Zinc-plated steel sheet> The galvanized steel sheet of the present invention is a galvanized steel sheet having a base steel sheet and a galvanized layer formed on the base steel sheet, characterized in that the base steel sheet has a steel structure in which, by area ratio, ferrite is less than 65%, the total of martensite and bainite is 25% or more, and retained austenite is 3% to 10% or less, and 70% or more of all martensite in the steel structure at 1 / 8 to 3 / 8 of the sheet thickness of the base steel sheet, by area ratio, is tempered martensite having carbides having an average grain size of 50 nm to 200 nm, the tensile strength is 780 MPa or more and less than 1180 MPa, and the yield ratio is 0.60 or more, and the integrated value of the amount of hydrogen released when the temperature of the base steel sheet from which the galvanized layer has been peeled off is raised from room temperature to 200°C is 0.45 mass ppm or less.

[0019] steel structure First, the area ratio of each structure in the base steel sheet of the present invention will be described. The area ratio of each structure refers to the area ratio of each constituent phase to the total area observed. The area ratio of each structure can be determined from image data obtained by polishing a steel sheet cross section parallel to the rolling direction, corroding it with a nital solution, and photographing it at a magnification of 1500 times with a SEM (scanning electron microscope). The measurement areas are a region 1 / 8 of the sheet thickness from the surface and a region 1 / 8 to 3 / 8 of the sheet thickness. In the image data, ferrite is black, bainite is black with island-like retained austenite or gray with aligned carbides, tempered martensite is light gray with fine randomly oriented carbides, and retained austenite is white. Here, as-quenched martensite and retained austenite are both white, so they can be difficult to distinguish from SEM images. For this reason, the area fraction of retained austenite is determined individually by measuring the X-ray diffraction intensity, and the area fraction of as-quenched martensite is calculated by subtracting it from the area fraction of the white area mentioned above. The area fraction of retained austenite is calculated from the ratio of the X-ray diffraction integrated intensity of the (200), (220), and (311) planes of fcc iron to the X-ray diffraction integrated intensity of the (200), (211), and (220) planes of bcc iron at 1 / 4 of the plate thickness. The retained austenite is calculated as a volume fraction by the above measurement, but the retained austenite is considered to be three-dimensionally homogeneous, and the volume fraction of the retained austenite is taken as the area fraction of the retained austenite. The martensite defined in the present invention includes both as-quenched martensite and tempered martensite, and may consist of as-quenched martensite and tempered martensite.

[0020] Ferrite area ratio: less than 65% If the area ratio of ferrite is 65% or more, a TS of 780 MPa or more may not be obtained. Therefore, the area ratio of ferrite is less than 65%, and preferably less than 60%. The lower limit is not particularly limited and may be 0%, but from the viewpoint of the balance between tensile strength and ductility, the area ratio of ferrite is preferably 5% or more, and more preferably 10% or more.

[0021] Total area ratio of martensite (including tempered martensite) and bainite: 25% or more Martensite is a hard structure that is generated from austenite at a low temperature below the martensitic transformation start point (Ms point). In the present invention, martensite includes not only as-quenched martensite (as-quenched martensite) but also tempered martensite obtained by tempering the generated martensite at a predetermined temperature. Bainite is formed from austenite at a relatively low temperature equal to or higher than the Ms point, and is a hard structure in which fine carbides are dispersed in needle-like or plate-like ferrite. Martensite and bainite are structures that contribute to the strength of the steel plate of the present invention, and if the total area ratio is less than 25%, a TS of 780 MPa or more may not be obtained. Therefore, the total area ratio of martensite and bainite is 25% or more, preferably 30% or more. Note that only one of martensite and bainite may be in the above range. There is no particular upper limit, but the total area ratio of martensite (including tempered martensite) and bainite is preferably 85% or less, more preferably 80% or less, from the viewpoint of more suitably controlling the balance between TS and ductility.

[0022] Area ratio of retained austenite: 3% to 10% If the steel contains an excessive amount of retained austenite, during bending or punching, the steel may undergo processing-induced transformation into hard martensite, which may promote crack generation and deteriorate bendability and hole expandability. This effect becomes significant when the retained austenite content exceeds 10%. Therefore, the area ratio of the retained austenite is 10% or less. The area ratio of the retained austenite is preferably 9% or less, and more preferably 8% or less. On the other hand, when the retained austenite content is less than 3%, sufficient ductility cannot be obtained. Therefore, the retained austenite content is 3% or more. The area ratio of the retained austenite is preferably 4% or more, and more preferably 5% or more.

[0023] As long as the contents of ferrite, martensite, bainite and retained austenite satisfy the above ranges, the remaining structure may contain other structures at an area ratio of 5% or less. Examples of other structures include pearlite.

[0024] In terms of area ratio, 70% or more of the total martensite in the steel structure at 1 / 8 to 3 / 8 of the plate thickness of the base steel plate: Tempered martensite having carbides with an average grain size of 50 nm to 200 nm In the present invention, by controlling the area ratio of the total martensite contained in the structure at 1 / 8 to 3 / 8 of the plate thickness of the base steel plate so that 70% or more is tempered martensite having carbides of a specified size, a high yield ratio can be obtained through precipitation strengthening. At the same time, by utilizing the fine carbides as hydrogen trapping sites in the steel and reducing diffusible hydrogen, it is possible to achieve both excellent hydrogen embrittlement resistance. In order to fully obtain these effects, the area ratio of tempered martensite having carbides of a predetermined size in the total martensite contained in the structure at 1 / 8 to 3 / 8 of the sheet thickness of the base steel sheet is 70% or more, preferably 80% or more, and may be 100%. This effect is obtained by setting the carbide size to a range of average grain size of 50 nm to 200 nm. In general, when the volume fraction of precipitates is constant, the smaller the grain size of the precipitates, the more advantageous it is for precipitation strengthening. In addition, from the viewpoint of hydrogen trapping, since the larger the surface area of ​​the carbides, the more advantageous it is, so that when the volume fraction is constant, the smaller the grain size of the carbides, the more preferable it is. Furthermore, when the carbides become coarse, it causes deterioration of bending property. Therefore, the average grain size of the carbides is 200 nm or less. On the other hand, if the average grain size of the carbides is less than 50 nm, the volume fraction of the carbides decreases, and the effects of precipitation strengthening and hydrogen trapping required for the present invention may not be sufficiently obtained. For the above reasons, in the present invention, tempered martensite having carbides with an average grain size of 50 nm or more and 200 nm or less is set to 70% or more of the total martensite in 1 / 8 to 3 / 8 of the sheet thickness of the base steel sheet. Here, the average particle size is the average value of the major axis length and the minor axis length when the particle is approximated as an ellipse. The average particle size can be measured by the method shown in the Examples, for example.

[0025] The cumulative amount of hydrogen released when the base steel sheet from which the coating layer has been peeled off is heated from room temperature to 200°C: 0.45 mass ppm or less In the galvanized steel sheet of the present invention, by controlling the amount of carbides in martensite to fall within the above-mentioned range, hydrogen that has entered the steel during the manufacturing process is effectively trapped, thereby reducing diffusible hydrogen, and the steel sheet has excellent bendability, stretch flangeability, and hydrogen embrittlement resistance. In the present invention, the amount of diffusible hydrogen in steel is defined as the integrated value of the amount of hydrogen released when a base steel sheet from which a plating layer (a zinc plating layer, and if a metal plating layer described below is formed, also includes the metal plating layer) has been peeled off is heated from room temperature (15 to 35°C) to 200°C at a rate of 200°C / h. If the diffusible hydrogen content exceeds 0.45 ppm by mass, excellent bendability, stretch flangeability, and hydrogen embrittlement resistance may not be obtained, and therefore the diffusible hydrogen content is 0.45 ppm by mass or less, and preferably 0.40 ppm by mass or less. The lower limit is not particularly limited, but since the smaller the amount of diffusible hydrogen, the more preferable, it may be set to 0 ppm by mass.

[0026] When the base steel sheet from which the coating layer has been peeled off is heated from room temperature to 600°C, the cumulative amount of hydrogen released in the temperature range of 350 to 600°C is 0.05 mass ppm or more (optimal conditions) The galvanized steel sheet of the present invention is designed to reduce diffusible hydrogen by effectively trapping hydrogen that has entered the steel during the manufacturing process by controlling the amount of carbides in the martensite to fall within the above-mentioned range. Hydrogen trapped in the carbides is less likely to be desorbed from the steel than diffusible hydrogen, and is not released by heating up to 200°C, but is released at 350°C or higher. In order to fully obtain the effects of the present invention, when a steel sheet from which a plating layer (a zinc plating layer, and if a metal plating layer described below is formed, also including the metal plating layer) has been peeled off is heated from room temperature (15 to 35°C) to 600°C at a rate of 200°C / h, the integrated value of hydrogen released at 350 to 600°C is preferably 0.05 mass ppm or more. More preferably, it is 0.06 mass ppm or more, and even more preferably, it is 0.07 mass ppm or more. There is no particular upper limit, but the integrated value of the amount of hydrogen released at 350 to 600° C. may be 1.00 mass ppm or less.

[0027] The above-mentioned method for quantifying hydrogen in steel involves taking a test piece for hydrogen analysis measuring about 5 x 30 mm from a galvanized steel sheet, removing the galvanized layer from the surface (including the metal plating layer if one is formed) using a precision grinder, quickly placing it in a quartz tube whose atmosphere has been replaced with Ar gas, heating it to 600°C at a heating rate of 200°C / h, and measuring the amount of hydrogen released during heating using a gas chromatograph. The integrated value of the amount of hydrogen released in the temperature range from room temperature to 200°C is calculated as the "amount of diffusible hydrogen," and the integrated value of the amount of hydrogen released in the temperature range from 350°C to 600°C is calculated as the "amount of trapped hydrogen." Here, the measurement of the amount of hydrogen is preferably performed after the manufacturing of the steel sheet is completed. That is, the measurement of the amount of diffusible hydrogen is preferably performed after the manufacturing of the steel sheet is completed. Also, the measurement of the amount of trapped hydrogen is preferably performed after the manufacturing of the steel sheet is completed. Moreover, it is more preferable that the measurement of the amount of diffusible hydrogen and the amount of trapped hydrogen be carried out within 72 hours after the steel sheet first reaches room temperature (40° C. or lower) after the reheating step specified in the present invention.

[0028] Zinc plating layer The galvanized steel sheet of the present invention has a galvanized layer on a base steel sheet, and the galvanized layer may be a galvannealed layer, a hot-dip galvanized layer, or a galvannealed layer.

[0029] The zinc-plated steel sheet of the present invention has a zinc plating layer (second plating layer when a metal plating layer (first plating layer) is formed) formed on the base steel sheet as the outermost layer (on the surface of the base steel sheet or on the surface of the metal plating layer if a metal plating layer is formed), and this zinc plating layer may be provided on only one surface of the base steel sheet, or on both surfaces. That is, the zinc-plated steel sheet of the present invention has a base steel sheet on which a second plating layer (zinc plating layer, aluminum plating layer, etc.) is formed, or may have a base steel sheet on which a metal plating layer (first plating layer (excluding the second plating layer of the zinc plating layer)) and a second plating layer (zinc plating layer, aluminum plating layer, etc.) are formed in that order on the base steel sheet.

[0030] The galvanized layer referred to here refers to a plating layer whose main component is Zn (Zn content of 50.0% or more), and examples thereof include a galvanized layer such as a hot-dip galvanized layer and an alloyed galvanized layer such as an alloyed hot-dip galvanized layer.

[0031] Here, the hot-dip galvanized layer (galvanized layer) is preferably composed of, for example, Zn, 20.0 mass% or less of Fe, and 0.001 mass% to 1.0 mass% of Al. The hot-dip galvanized layer may optionally contain one or more elements selected from the group consisting of Pb, Sb, Si, Sn, Mg, Mn, Ni, Cr, Co, Ca, Cu, Li, Ti, Be, Bi, and REM in a total amount of 0.0 mass% to 3.5 mass%. The Fe content of the hot-dip galvanized layer is more preferably less than 7.0 mass%. The remainder other than the above elements is unavoidable impurities.

[0032] In addition, the galvannealed layer (galvannealed layer) is preferably composed of, for example, 20% by mass or less of Fe and 0.001% by mass or more and 1.0% by mass or less of Al. In addition, the galvannealed layer may optionally contain one or more elements selected from the group consisting of Pb, Sb, Si, Sn, Mg, Mn, Ni, Cr, Co, Ca, Cu, Li, Ti, Be, Bi and REM in a total amount of 0.0% by mass or more and 3.5% by mass or less. The Fe content of the galvannealed layer is more preferably 7.0% by mass or more, and more preferably 8.0% by mass or more. The Fe content of the galvannealed layer is more preferably 15.0% by mass or less, and more preferably 13.0% by mass or less. The remainder other than the above elements is unavoidable impurities.

[0033] In addition, the coating weight of the zinc-plated layer on one side is not particularly limited, but is preferably 20 g / m 2 The coating weight of the zinc-plated layer on one side is preferably 80 g / m or more. 2 It is preferable that:

[0034] The plating weight of the zinc plating layer is measured as follows. That is, a treatment solution is prepared by adding 0.6 g of a corrosion inhibitor for Fe (Ivit 700BK (registered trademark) manufactured by Asahi Chemical Industry Co., Ltd.) to 1 L of a 10 mass % aqueous hydrochloric acid solution. Next, a steel sheet to be used as a test material is immersed in the treatment solution to dissolve the zinc plating layer. The amount of mass loss of the test material before and after dissolution is then measured, and this value is divided by the surface area of ​​the base steel sheet (the surface area of ​​the part that was covered with plating) to obtain the plating coverage (g / m 2 ) is calculated.

[0035] Ingredient composition Next, a preferred composition of the steel sheet (base steel sheet (hereinafter, sometimes simply referred to as steel sheet)) constituting the galvanized steel sheet will be described. Note that "%" representing the content of the component elements means "mass %" unless otherwise specified.

[0036] C: 0.080% or more and 0.300% or less C improves hardenability and makes it easier to obtain martensite and bainite. In addition, by precipitating in the structure as fine carbides, it is possible to trap hydrogen in the steel, reducing the amount of diffusible hydrogen and improving hydrogen embrittlement resistance. If the C content is less than 0.080%, it is not possible to achieve both the required strength and bendability. Therefore, the C content is preferably 0.080% or more, and more preferably 0.100% or more. On the other hand, if the C content exceeds 0.300%, the hydrogen trapping effect of fine carbides becomes saturated, and the strength of martensite becomes excessively high, which may impair ductility. Therefore, the C content is preferably 0.300% or less, and more preferably 0.250% or less.

[0037] Si: 0.20% or more and 2.00% or less, Silicon is an element effective in strengthening ferrite with excellent ductility, and also promotes the formation of retained austenite by suppressing the formation of coarse carbides when the steel sheet after annealing is held at a relatively low temperature, thereby contributing to improving the balance between strength and ductility. This effect cannot be sufficiently obtained when the Si content is less than 0.20%. Therefore, the Si content is 0.20% or more, and preferably 0.30% or more. On the other hand, if the Si content exceeds 2.00%, the carbide formation action becomes excessive, and fine carbides in martensite required for the present invention cannot be obtained, and diffusible hydrogen in the steel increases, so that the desired yield ratio and hydrogen embrittlement resistance of the present invention may not be obtained. Therefore, the Si content is preferably 2.00% or less, and more preferably 1.50% or less.

[0038] Mn: 1.00% or more and 4.00% or less Mn improves the hardenability of steel, making it easier to obtain martensite and bainite. If the Mn content is less than 1.00%, the area ratio of ferrite becomes excessive, and the required strength and yield ratio may not be obtained. Therefore, the Mn content is preferably 1.00% or more, and more preferably 1.50% or more. On the other hand, if the Mn content exceeds 4.00%, the strength of martensite becomes excessively high, and the formation of coarse MnS is promoted, so that excellent bendability may not be obtained. Therefore, the Mn content is preferably 4.00% or less, and more preferably 3.50% or less.

[0039] P:0.10% or less If P is contained in excess, it segregates at the prior austenite grain boundaries, embrittling the grain boundaries and causing deterioration of bendability. Therefore, the P content is preferably 0.10% or less, and more preferably 0.05% or less. The P content is preferably 0.03% or less, and more preferably 0.02% or less. Although there is no particular lower limit, since P is also an element effective in increasing the strength of the steel sheet by solid solution strengthening, in order to obtain such an effect, the P content is preferably 0.001% or more. The P content may be 0.002% or more, or may be 0.005% or more.

[0040] S: 0.0200% or less S forms inclusions such as MnS and causes deterioration of bendability, so the S content is preferably 0.0200% or less, and more preferably 0.0100% or less. Although there is no particular lower limit, due to constraints on production technology, the S content may be 0.0001% or more, may be 0.0002% or more, or may be 0.0004% or more.

[0041] Al: 0.003% or more and 0.100% or less In addition to being used as a deoxidizer, Al also contributes to solid solution strengthening of steel. If the Al content is less than 0.003%, these effects may not be obtained. Therefore, the Al content is preferably 0.003% or more. The Al content is preferably 0.005% or more, and more preferably 0.007% or more. On the other hand, if the Al content exceeds 0.100%, it leads to deterioration of slab quality during steelmaking, so the Al content is preferably 0.100% or less, and more preferably 0.050% or less.

[0042] N: 0.0100% or less N may form coarse nitrides, which may become the starting point for void generation and reduce bendability. By setting the N content to 0.0100% or less, it is possible to prevent N from forming coarse nitrides. Therefore, the N content is preferably 0.0100% or less, and more preferably 0.0060% or less. Although there is no particular lower limit, due to constraints on production technology, the N content may be set to 0.0005% or more.

[0043] The balance other than the above consists of Fe and unavoidable impurities.The steel sheet of the present invention preferably has a composition containing the above-mentioned components with the balance consisting of Fe and unavoidable impurities. The composition may further contain a predetermined amount of at least one element selected from the following group of elements. When the following optional elements are contained in an amount less than the preferred lower limit, the optional elements can be regarded as being contained as unavoidable impurities.

[0044] B: 0.0100% or less B is an element effective for improving the hardenability of steel. In order to improve the hardenability, the B content is preferably 0.0001% or more, more preferably 0.0002% or more, and even more preferably 0.0003% or more. The B content is preferably 0.0005% or more, and more preferably 0.0007% or more. In order to obtain better formability, when B is contained, the B content is preferably 0.0100% or less, more preferably 0.0050% or less, and even more preferably 0.0030% or less.

[0045] Ti: 0.200% or less Ti precipitates fine carbides and contributes to increasing strength and trapping hydrogen. There is no particular lower limit for Ti, but in order to obtain these effects, it is preferably 0.001% or more, more preferably 0.005% or more, and even more preferably 0.010% or more. On the other hand, if Ti is contained in excess, the carbides may become coarse and cause deterioration of bendability. Therefore, if Ti is contained, the Ti content is preferably 0.200% or less, more preferably 0.100% or less, and even more preferably 0.060% or less.

[0046] Nb: 0.200% or less Nb precipitates fine carbides and contributes to increasing strength and trapping hydrogen. There is no particular lower limit for Nb, but in order to obtain these effects, it is preferably 0.001% or more, more preferably 0.005% or more, and even more preferably 0.010% or more. On the other hand, if Nb is contained in excess, the carbides may become coarse and cause deterioration of bendability. Therefore, if Nb is contained, the Nb content is preferably 0.200% or less, more preferably 0.100% or less, and even more preferably 0.060% or less.

[0047] Sb: 0.200% or less Sb is an element effective in suppressing excessive decarburization of the steel sheet surface and preventing a decrease in the amount of martensite formed. To obtain such effects, the Sb content is preferably 0.001% or more, more preferably 0.002% or more, and even more preferably 0.005% or more. On the other hand, in order to obtain better toughness, when Sb is contained, the Sb content is preferably 0.200% or less, more preferably 0.060% or less, and further preferably 0.020% or less.

[0048] Sn: 0.200% or less Sn is an element that is effective in suppressing a decrease in the strength of steel by suppressing decarburization, denitrification, etc. In order to obtain such effects, the Sn content is preferably 0.001% or more, more preferably 0.002% or more, and even more preferably 0.005% or more. On the other hand, in order to obtain better impact resistance, when Sn is contained, the Sn content is preferably 0.200% or less, more preferably 0.060% or less, and further preferably 0.020% or less.

[0049] V:0.100% or less V precipitates fine carbides, and contributes to increasing strength and hydrogen trapping effect. There is no particular lower limit for V, but in order to obtain these effects, it is preferably 0.001% or more, more preferably 0.002% or more, and even more preferably 0.005% or more. The V content is preferably 0.007% or more, and more preferably 0.009% or more. On the other hand, if an excessive amount of V is contained, the carbides may become coarse and cause deterioration of bendability. Therefore, if V is contained, the V content is preferably 0.100% or less, more preferably 0.080% or less, and even more preferably 0.060% or less.

[0050] Cu:2.00% or less Cu is an element that improves hardenability and is effective for setting the area ratio of the hard phase within a more suitable range. To achieve this effect, the Cu content is preferably 0.005% or more, more preferably 0.010% or more, and even more preferably 0.020% or more. The Cu content is preferably 0.040% or more, and more preferably 0.060% or more. Furthermore, when Cu is contained, from the viewpoint of preventing an increase in costs, the Cu content is preferably 2.00% or less, more preferably 1.00% or less, and even more preferably 0.50% or less.

[0051] Cr:2.00% or less The addition of Cr can improve the hardenability and balance between strength and ductility. To obtain this effect, the Cr content is preferably 0.001% or more, more preferably 0.002% or more, and even more preferably 0.005% or more. The Cr content is preferably 0.007% or more, and more preferably 0.009% or more. Furthermore, when Cr is contained, from the viewpoint of preventing an increase in costs, the Cr content is preferably set to 2.00% or less, more preferably set to 1.00% or less, and further preferably set to 0.80% or less.

[0052] Ni: 2.00% or less The addition of Ni can improve the hardenability and balance between strength and ductility. To obtain this effect, the Ni content is preferably 0.005% or more, more preferably 0.010% or more, and even more preferably 0.020% or more. The Ni content is preferably 0.030% or more, and more preferably 0.040% or more. In addition, when Ni is contained, from the viewpoint of preventing an increase in costs, the Ni content is preferably 2.00% or less, more preferably 1.00% or less, and even more preferably 0.80% or less. The Ni content is preferably 0.60% or less, and more preferably 0.40% or less.

[0053] Mo: 1.00% or less The addition of Mo can provide a strength adjustment effect. To achieve this effect, the Mo content is preferably 0.005% or more, more preferably 0.01% or more, and even more preferably 0.02% or more. The Mo content is preferably 0.03% or more, and more preferably 0.04% or more. When Mo is contained, from the viewpoint of preventing an increase in costs, the Mo content is preferably 1.00% or less, more preferably 0.80% or less, and even more preferably 0.60% or less. The Mo content is preferably 0.50% or less, and more preferably 0.40% or less.

[0054] Ta:0.100% or less The addition of Ta can provide an effect of improving strength. To obtain this effect, the Ta content is preferably 0.001% or more, more preferably 0.002% or more, and even more preferably 0.003% or more. Furthermore, when Ta is contained, from the viewpoint of preventing an increase in costs, the Ta content is preferably 0.100% or less, more preferably 0.050% or less, and further preferably 0.020% or less, and preferably 0.010% or less, and more preferably 0.008% or less.

[0055] W: 0.500% or less The addition of W can improve the strength. To achieve this effect, the W content is preferably 0.001% or more, more preferably 0.002% or more, and even more preferably 0.003% or more. The W content is preferably 0.005% or more, and more preferably 0.007% or more. In addition, when W is contained, from the viewpoint of preventing an increase in costs, the W content is preferably 0.500% or less, more preferably 0.450% or less, and even more preferably 0.400% or less. The W content is preferably 0.350% or less, and more preferably 0.300% or less.

[0056] Zr: 0.020% or less The addition of Zr can improve the ultimate deformability of the steel sheet and improve the stretch flangeability. To achieve this effect, the Zr content is preferably 0.0005% or more, more preferably 0.0010% or more, and even more preferably 0.0015% or more. Furthermore, when Zr is contained, from the viewpoint of preventing an increase in costs, the Zr content is preferably 0.020% or less, more preferably 0.010% or less, and further preferably 0.0050% or less.

[0057] Ca:0.0200% or less By containing Ca, the morphology of sulfides can be controlled, and ductility and toughness can be further improved. In order to obtain better ductility, when Ca is contained, the Ca content is preferably 0.0200% or less. The Ca content is more preferably 0.0100% or less, and further preferably 0.0050% or less. The Ca content is preferably 0.0040% or less, and preferably 0.0030% or less. The lower limit of the Ca content is not particularly limited and may be 0.0000%, but due to restrictions on production technology, the Ca content is preferably 0.0001% or more. From the viewpoint of controlling the morphology of the above-mentioned sulfides and further improving ductility and toughness, the Ca content is more preferably 0.0005% or more.

[0058] Mg: 0.0200% or less The Mg content of 0.0001% or more can control the morphology of sulfides and improve ductility and toughness, more preferably 0.0005% or more, and further preferably 0.001% or more. In order to obtain better ductility, when Mg is contained, the Mg content is preferably 0.0200% or less, more preferably 0.0100% or less, and further preferably 0.0050% or less.

[0059] Zn: 0.020% or less The addition of Zn can improve the ultimate deformability of the steel sheet and improve the stretch flangeability. To achieve this effect, the Zn content is preferably 0.001% or more, more preferably 0.002% or more, and even more preferably 0.003% or more. Furthermore, when Zn is contained, from the viewpoint of preventing an increase in costs, the Zn content is preferably 0.020% or less, more preferably 0.010% or less, and further preferably 0.008% or less.

[0060] Co:0.020% or less The addition of Co can improve the ultimate deformability of the steel sheet and improve the stretch flangeability. To achieve this effect, the Co content is preferably 0.001% or more, more preferably 0.002% or more, and even more preferably 0.003% or more. Furthermore, when Co is contained, from the viewpoint of preventing an increase in costs, the Co content is preferably 0.020% or less, more preferably 0.010% or less, and further preferably 0.008% or less.

[0061] Content of Ce, Se, Te, Ge, As, Sr, Cs, Hf, Pb, Bi, REM (excluding Ce): 0.0200% or less The addition of these elements can improve the ultimate deformability of the steel sheet and improve the stretch flangeability. To achieve this effect, it is preferable to contain at least one of these elements in an amount of 0.0001% or more. On the other hand, from the viewpoint of preventing an increase in costs, when at least one of these elements is contained, the content of each is preferably 0.0200% or less. Ce is more preferably 0.0002% or more, and even more preferably 0.0005% or more. Ce is more preferably 0.0150% or less, and even more preferably 0.0100% or less. Ce is preferably 0.0080% or less, and even more preferably 0.0060% or less. Se is preferably 0.0002% or more, and more preferably 0.0005% or more. Se is preferably 0.0007% or more, and more preferably 0.0009% or more. Se is preferably 0.0150% or less, and more preferably 0.0100% or less. Se is preferably 0.0080% or less, and more preferably 0.0060% or less. Te is more preferably 0.0002% or more, and even more preferably 0.0005% or more. Te is preferably 0.0007% or more, and even more preferably 0.0009% or more. Te is more preferably 0.0150% or less, and even more preferably 0.0100% or less. Ge is more preferably 0.0002% or more, and even more preferably 0.0005% or more. Ge is preferably 0.0007% or more, and even more preferably 0.0009% or more. Ge is more preferably 0.0150% or less, and even more preferably 0.0100% or less. As is more preferably 0.0002% or more, and even more preferably 0.0005% or more. As is preferably 0.0007% or more, and even more preferably 0.0009% or more. As is more preferably 0.0150% or less, and even more preferably 0.0100% or less. Sr is more preferably 0.0002% or more, and even more preferably 0.0005% or more. Sr is preferably 0.0007% or more, and even more preferably 0.0009% or more. Sr is more preferably 0.0150% or less, and even more preferably 0.0100% or less. Cs is more preferably 0.0002% or more, and even more preferably 0.0005% or more. Cs is preferably 0.0007% or more, and even more preferably 0.0009% or more. Cs is more preferably 0.0150% or less, and even more preferably 0.0100% or less. Hf is more preferably 0.0002% or more, and even more preferably 0.0005% or more. Hf is preferably 0.0007% or more, and even more preferably 0.0009% or more. Hf is more preferably 0.0150% or less, and even more preferably 0.0100% or less. Pb is more preferably 0.0002% or more, and even more preferably 0.0005% or more. Pb is preferably 0.0007% or more, and even more preferably 0.0009% or more. Pb is more preferably 0.0150% or less, and even more preferably 0.0100% or less. Pb is preferably 0.0080% or less, and even more preferably 0.0060% or less. Bi is more preferably 0.0002% or more, and even more preferably 0.0005% or more. Bi is preferably 0.0007% or more, and even more preferably 0.0009% or more. Bi is more preferably 0.0150% or less, and even more preferably 0.0100% or less. Bi is preferably 0.0080% or less, and even more preferably 0.0060% or less. The REM is more preferably 0.0002% or more, and even more preferably 0.0005% or more. The REM is preferably 0.0007% or more, and even more preferably 0.0009% or more. The REM is more preferably 0.0150% or less, and even more preferably 0.0100% or less. The REM specified in the present invention excludes the above-mentioned Ce. In the present invention, REM refers to scandium (Sc), which has atomic number 21, yttrium (Y), which has atomic number 39, and the lanthanoids ranging from lanthanum (La), which has atomic number 57, to lutetium (Lu), which has atomic number 71. The REM concentration in the present invention refers to the total content of one or more elements selected from the above-mentioned REMs. The REM is not particularly limited, but is preferably Sc, Y or La.

[0062] surface soft layer In the base steel sheet of the galvanized steel sheet according to one embodiment of the present invention, it is preferable that the surface layer has a soft surface layer. The soft surface layer contributes to suppressing the progression of bending cracks during press forming and vehicle body collision, thereby further improving bending fracture resistance. The soft surface layer means a decarburized layer, and is a surface region having a Vickers hardness of 85% or less of the Vickers hardness of a cross section (plane parallel to the steel sheet surface) at 1 / 4 of the sheet thickness. Here, the soft surface layer is formed to a thickness of 200 μm or less from the surface of the base steel sheet in the sheet thickness direction. The region in which the soft surface layer is formed is preferably 150 μm or less, more preferably 120 μm or less, from the surface of the base steel sheet in the sheet thickness direction. There is no particular lower limit for the thickness of the soft surface layer, but it is preferably 7 μm or more, more preferably 14 μm or more, and even more preferably 17 μm or more. The soft surface layer is preferably 30 μm or more, more preferably 40 μm or more. The 1 / 4 sheet thickness position of the base steel sheet where the Vickers hardness is measured is a non-surface soft layer (a layer that does not satisfy the hardness conditions of the surface soft layer defined in the present invention). Vickers hardness is measured based on JIS Z 2244-1 (2020) at a load of 10 gf.

[0063] Nano-hardness of the soft surface layer In the galvanized steel sheet of the present invention, when the nanohardness is measured at 300 or more points in a 50 μm × 50 μm region of the sheet surface at a position 1 / 4 of the thickness direction depth of the soft surface layer and a position 1 / 2 of the thickness direction depth from the surface of the base steel sheet, it is preferable that the ratio of the number of measurements where the nanohardness of the sheet surface at a position 1 / 4 of the thickness direction depth of the soft surface layer from the surface of the base steel sheet is 7.0 GPa or more to the total number of measurements is 0.10 or less, and further, the standard deviation σ of the nanohardness of the sheet surface at a position 1 / 4 of the thickness direction depth of the soft surface layer from the surface of the base steel sheet is 1.8 GPa or less, and further, the standard deviation σ of the nanohardness of the sheet surface at a position 1 / 2 of the thickness direction depth of the soft surface layer from the surface of the base steel sheet is 2.2 GPa or less.

[0064] When the proportion of pieces with a nano-hardness of 7.0 GPa or more relative to the total number of measurements is 0.10 or less, this means that the proportion of hard structures (such as martensite), inclusions, etc. is small, making it possible to further suppress the generation and connection of voids and the progression of cracks in the hard structures (such as martensite) and inclusions during press forming and collision, and resulting in excellent R / t and SFmax.

[0065] Furthermore, in order to obtain excellent bendability during press forming and excellent bending fracture properties during collision, it is preferable that the standard deviation σ of the nanohardness of the sheet surface at a position 1 / 4 of the sheet thickness direction depth of the soft surface layer from the surface of the base steel sheet is 1.8 GPa or less, and further, the standard deviation σ of the nanohardness of the sheet surface at a position 1 / 2 of the sheet thickness direction depth of the soft surface layer from the surface of the base steel sheet is 2.2 GPa or less. When the standard deviation σ of the nanohardness of the sheet surface at a position 1 / 4 of the way through the thickness of the soft surface layer from the surface of the base steel sheet is 1.8 GPa or less, and further, when the standard deviation σ of the nanohardness of the sheet surface at a position 1 / 2 of the way through the thickness of the soft surface layer from the surface of the base steel sheet is 2.2 GPa or less, this means that the difference in microstructural hardness in the microregion is small.Since the difference in microstructural hardness in the microregion is small, it is possible to further suppress the generation and connection of voids during press forming and collision, as well as the progression of cracks, and obtain excellent R / t and SFmax. Furthermore, a preferred range of the standard deviation σ of the nanohardness of the sheet surface at 1 / 4 of the sheet thickness direction depth of the soft surface layer from the surface of the base steel sheet is 1.7 GPa or less. The standard deviation σ of the nanohardness of the sheet surface at 1 / 4 of the sheet thickness direction depth of the soft surface layer from the surface of the base steel sheet is more preferably 1.3 GPa or less. Although there is no particular lower limit, the standard deviation σ of the nanohardness of the sheet surface at 1 / 4 of the sheet thickness direction depth of the soft surface layer from the surface of the base steel sheet may be 0.5 GPa or more. A preferred range of the standard deviation σ of the nano-hardness of the sheet surface at 1 / 2 the depth in the sheet thickness direction of the soft surface layer from the surface of the base steel sheet is 2.1 GPa or less. The standard deviation σ of the nano-hardness of the sheet surface at 1 / 2 the depth in the sheet thickness direction of the soft surface layer from the surface of the base steel sheet is more preferably 1.7 GPa or less. Although there is no particular lower limit, the standard deviation σ of the nano-hardness of the sheet surface at 1 / 2 the depth in the sheet thickness direction of the soft surface layer from the surface of the base steel sheet may be 0.6 GPa or more.

[0066] Here, the nano-hardness of the plate surface at the 1 / 4 and 1 / 2 positions in the plate thickness direction depth is a hardness measured by the following method. First, after peeling off the zinc plating layer, for steel sheets on which a metal plating layer such as a metal electroplating layer is formed, mechanical polishing is performed from the surface of the base steel sheet to a position 1 / 4 of the depth in the sheet thickness direction of the soft surface layer after peeling off the metal plating layer, buffing with diamond and alumina, and further colloidal silica polishing. Using a Hysitron tribo-950, the nano hardness is measured with a Berkovich-shaped diamond indenter under the conditions of load: 500 μN, measurement area: 50 μm × 50 μm, and impact spacing: 2 μm. In addition, the surface soft layer is mechanically polished up to 1 / 2 the depth in the plate thickness direction, buffed with diamond and alumina, and then polished with colloidal silica.Then, using a Hysitron tribo-950, the nano hardness is measured with a Berkovich-shaped diamond indenter under the following conditions: load: 500μN, measurement area: 50μm×50μm, and impact spacing: 2μm. Nano hardness is measured at 300 or more points at a position 1 / 4 of the way through the plate thickness, and also at 300 or more points at a position 1 / 2 of the way through the plate thickness. For example, if the thickness of the surface soft layer is 100 μm, the 1 / 4 position is 25 μm from the surface of the surface soft layer, and the 1 / 2 position is 50 μm from the surface of the surface soft layer. At this 25 μm position, nano hardness is measured at 300 or more points, and also at the 50 μm position, nano hardness is measured at 300 or more points.

[0067] Metal plating layer Furthermore, the galvanized steel sheet according to one embodiment of the present invention preferably has a metal plating layer (first plating layer, pre-plating layer) (note that the metal plating layer excludes the galvanized layer of a hot-dip galvanized layer and an alloyed hot-dip galvanized layer) formed between the base steel sheet and the galvanized layer on one or both sides of the base steel sheet. The metal plating layer is preferably a metal electroplated layer, and the following description will be given taking a metal electroplated layer as an example. By forming a metal electroplating layer on the base steel sheet, the outermost metal electroplating layer contributes to suppressing the occurrence of bending cracks during press forming and vehicle collisions, thereby further improving the bending fracture resistance. In the present invention, the thickness of the soft layer can be increased and the axial collapse characteristics can be made very excellent by setting the dew point in the soaking step to -5°C or higher. In this regard, in the present invention, by having a metal plating layer, even if the dew point is less than -5°C and the soft layer thickness is small, the axial collapse characteristics can be obtained equivalent to that in the case of a thick soft layer.

[0068] Metal species of the metal electroplating layer include Cr, Mn, Fe, Co, Ni, Cu, Ga, Ge, As, Ru, Rh, Pd, Ag, Cd, In, Sn, Sb, Os, Ir, Pt The metal may be any of Au, Hg, Ti, Pb, and Bi, but Fe is more preferable. In the following, an Fe-based electroplating layer will be described as an example, but the following conditions for Fe can be similarly adopted for other metals.

[0069] The adhesion weight of the Fe-based electroplating layer is 0g / m 2 More than 2.0 g / m 2 The upper limit of the coating weight of the Fe-based electroplating layer per side of the base steel sheet is not particularly limited, but from the viewpoint of cost, the coating weight of the Fe-based electroplating layer per side is set to 60 g / m 2 The coating weight of the Fe-based electroplating layer is preferably 50 g / m 2 More preferably, it is 40 g / m or less. 2 More preferably, it is 30 g / m or less. 2 The following is the result.

[0070] The adhesion weight of the Fe-based electroplating layer is measured as follows. A sample of 10 x 15 mm size is taken from the Fe-based electroplated steel sheet and embedded in resin to create a cross-section embedded sample. Three random locations on the cross-section are observed using a scanning electron microscope (SEM) at an accelerating voltage of 15 kV and a magnification of 2000 to 10000 times depending on the thickness of the Fe-based electroplating layer, and the average thickness of the three fields of view is multiplied by the iron density to convert it into the adhesion weight of the Fe-based electroplating layer per side.

[0071] As the Fe-based electroplating layer, in addition to pure Fe, alloy plating layers such as Fe-B alloy, Fe-C alloy, Fe-P alloy, Fe-N alloy, Fe-O alloy, Fe-Ni alloy, Fe-Mn alloy, Fe-Mo alloy, Fe-W alloy, etc. can be used. The composition of the Fe-based electroplating layer is not particularly limited, but it is preferable that the composition contains one or more elements selected from the group consisting of B, C, P, N, O, Ni, Mn, Mo, Zn, W, Pb, Sn, Cr, V and Co in a total of 10 mass% or less, with the balance being Fe and unavoidable impurities. By making the amount of elements other than Fe 10 mass% or less in total, it is possible to prevent a decrease in electrolysis efficiency and form the Fe-based electroplating layer at low cost. In the case of an Fe-C alloy, the content of C is preferably 0.08 mass% or less.

[0072] <Manufacturing method of zinc-plated steel sheet> Next, a method for producing a galvanized steel sheet according to an embodiment of the present disclosure will be described. Note that the temperatures when heating or cooling a steel slab (steel material), a steel sheet, etc. shown below refer to the surface temperatures of the steel slab (steel material), a steel sheet, etc., unless otherwise specified.

[0073] The method for producing a galvanized steel sheet of the present invention includes a hot rolling process in which a slab having the above-mentioned chemical composition is heated to a temperature range of 1100 to 1350°C, hot rolled at a finish rolling end temperature of 800 to 950°C, and coiled at a coiling temperature of 650°C or less, a reduction process in which the steel sheet after the hot rolling process is held at 700°C or higher in a reducing atmosphere with a hydrogen concentration of 8 volume% to 30 volume% for 20 s or more, and a soaking process in which the steel sheet after the reduction process is held at 750°C or higher in a soaking atmosphere with a hydrogen concentration of 0.2 volume% to 8 volume% for 20 s to 300 s. the first cooling step of cooling the steel sheet after the soaking step; the galvanizing step of forming a galvanized layer on the surface of the steel sheet after the first cooling step; the second cooling step of cooling the steel sheet after the galvanizing step to a cooling stop temperature of 100 to 300°C at an average cooling rate of 20°C / s or less from a temperature range of 350 to 450°C to (Ms point - 100°C) and by retaining the steel sheet in a temperature range of 100 to 350°C for 5 s or more; and the reheating step of retaining the steel sheet after the second cooling step in a temperature range of not less than the cooling stop temperature and not more than 450°C for 5 to 600 s.

[0074] [Hot rolling process] The slab is hot-rolled under the following conditions.

[0075] Slab heating temperature: 1100~1350℃ In order to dissolve carbides and reduce the rolling load, the slab heating temperature is set to 1100° C. or higher. The slab heating temperature is preferably 1150° C. or higher. In order to prevent an increase in scale loss, the slab heating temperature is set to 1350° C. or lower, and preferably 1300° C. or lower.

[0076] Finish rolling temperature: 800~950℃ If the finish rolling end temperature is less than 800°C, ferrite transformation occurs during rolling, and extended ferrite is generated on the surface layer of the hot-rolled sheet, which may remain in the next process and deteriorate the final bendability. Therefore, the finish rolling end temperature is 800°C or higher, preferably 850°C or higher. On the other hand, if the finish rolling end temperature exceeds 950°C, the crystal grains become coarse, which may cause insufficient strength and deterioration of bendability. Therefore, the finish rolling end temperature is 950°C or lower, preferably 930°C or lower.

[0077] Winding temperature: 650℃ or less If the coiling temperature exceeds 650°C, the carbides in the hot-rolled steel sheet will become coarse and will not completely melt before the soaking step, which may cause deterioration in bendability. Therefore, the coiling temperature is 650°C or less, and preferably 600°C or less. There is no particular lower limit to the coiling temperature, but from the viewpoint of suppressing the occurrence of defective shape of the steel sheet and preventing the steel sheet from becoming excessively hard, it is preferably 400°C or more.

[0078] [Cold rolling process (optimal conditions)] Before the base steel sheet after the hot rolling process (hot rolling process) is subjected to the reducing process, cold rolling may be performed as necessary. The cold rolling in the cold rolling process is performed before the oxidation process when an oxidation treatment is performed in the oxidation process described below, and is performed before the pre-plating process when metal plating is performed in the pre-plating process. When cold rolling is performed, it is preferable that the hot-rolled steel sheet obtained after the hot rolling process (hot rolling process) is subjected to preliminary treatment such as pickling and degreasing by a known method before cold rolling.

[0079] Reduction of 20% or more When cold rolling is performed, the reduction rate (cumulative reduction rate) is not particularly limited, but in order to promote the recrystallization of ferrite, it is preferably 20% or more, and more preferably 30% or more. The upper limit of the reduction rate is not particularly limited, but it is preferably 80% or less.

[0080] [Pre-plating (metal plating, metal electroplating, first plating) process (optimal conditions)] In one embodiment of the present invention, the base steel sheet may be subjected to a pre-plating (metal plating) treatment after the above-mentioned hot rolling step (after the cold rolling step if cold rolling is performed) and before the reducing step to form a pre-annealed metal-plated steel sheet (pre-annealed metal-electroplated steel sheet) in which a metal plating layer such as a metal electroplating layer is formed on one or both sides of the base steel sheet. Note that the metal plating referred to here does not include zinc plating (second plating). The metal plating method is not particularly limited, but as described above, it is preferable that the metal plating layer formed on the base steel sheet is a metal electroplating layer, and therefore it is preferable to carry out a metal electroplating process. For example, when an Fe-based electroplating bath is used, a sulfuric acid bath, a hydrochloric acid bath, or a mixture of both can be used. The deposition weight of the pre-annealed metal electroplating layer can be adjusted by the current application time, etc. Note that the pre-annealed metal electroplated steel sheet means that the metal electroplating layer has not been subjected to the oxidation step, reduction step, and soaking step, and does not exclude a form in which a hot-rolled steel sheet or a cold-rolled steel sheet has been annealed in advance before the metal electroplating process.

[0081] Here, the metal species of the electroplating layer are Cr, Mn, Fe, Co, Ni, Cu, Ga, Ge, As, Ru, Rh, Pd, Ag, Cd, In, Sn, Sb, Os, Ir, Pt The metal may be any of Au, Hg, Ti, Pb, and Bi, but Fe is more preferable. In the following, Fe-based electroplating is used as an example, but the following conditions for Fe-based electroplating can be similarly adopted for other metal-based electroplating.

[0082] The Fe ion content in the Fe-based electroplating bath before the start of current application is 2+ The Fe ion content in the Fe-based electroplating bath is preferably 0.5 mol / L or more. 2+ A sufficient amount of Fe can be obtained if the Fe ion content in the Fe-based electroplating bath before the start of current application is 0.5 mol / L or more. In order to obtain a sufficient amount of Fe, the Fe ion content in the Fe-based electroplating bath before the start of current application is preferably 2.0 mol / L or less.

[0083] The Fe-based electroplating bath may contain Fe ions and at least one element selected from the group consisting of B, C, P, N, O, Ni, Mn, Mo, Zn, W, Pb, Sn, Cr, V, and Co. The total content of these elements in the Fe-based electroplating bath is preferably such that the total content of these elements in the Fe-based electroplating layer before annealing is 10 mass% or less. The metal elements may be contained as metal ions, and the nonmetal elements may be contained as part of boric acid, phosphoric acid, nitric acid, organic acid, etc. The iron sulfate plating solution may also contain a conductivity aid such as sodium sulfate or potassium sulfate, a chelating agent, or a pH buffer.

[0084] Other conditions for the Fe-based electroplating bath are not particularly limited. The temperature of the Fe-based electroplating solution is preferably 30°C or higher in consideration of the ability to maintain a constant temperature. The temperature of the Fe-based electroplating solution is preferably 85°C or lower. The pH of the Fe-based electroplating bath is not particularly specified, but is preferably 1.0 or higher in consideration of preventing a decrease in current efficiency due to hydrogen generation, and is preferably 3.0 or lower in consideration of the electrical conductivity of the Fe-based electroplating bath. The current density is preferably 10 A / dm from the viewpoint of productivity. 2 From the viewpoint of easily controlling the deposition weight of the Fe-based electroplating layer, it is preferable to set the current to 150 A / dm or more. 2 The sheet threading speed is preferably 5 mpm or more from the viewpoint of productivity, and is preferably 150 mpm or less from the viewpoint of stably controlling the amount of adhesion.

[0085] As a treatment before the Fe-based electroplating treatment, a degreasing treatment and water washing for cleaning the steel sheet surface, and further, a pickling treatment and water washing for activating the steel sheet surface can be performed. Following these pretreatments, the Fe-based electroplating treatment is performed. The method of the degreasing treatment and water washing is not particularly limited, and a normal method can be used. In the pickling treatment, various acids such as sulfuric acid, hydrochloric acid, nitric acid, and mixtures thereof can be used. Among them, sulfuric acid, hydrochloric acid, or mixtures thereof are preferable. The concentration of the acid is not particularly specified, but considering the ability to remove the oxide film and the prevention of roughness (surface defects) due to excessive pickling, it is preferable that the concentration is 1 to 20 mass%. In addition, the pickling treatment solution may contain an antifoaming agent, a pickling promoter, a pickling inhibitor, etc.

[0086] [Oxidation process (optimal conditions)] The steel sheet after the hot rolling process or the steel sheet after the cold rolling process in the case where the cold rolling process is performed may be subjected to an oxidation treatment in an oxidation step before a reduction step described later. By performing the oxidation treatment in the oxidation step, an iron oxide layer is formed on the surface of the steel sheet, and a reduced iron layer is formed during the subsequent annealing in a reducing atmosphere, thereby improving the wettability of the steel sheet.

[0087] Oxygen concentration: 1000 ppm by volume or more and 30000 ppm by volume or less When performing oxidation treatment in the oxidation step, if the oxygen concentration in the atmosphere is less than 1000 ppm by volume, the formation of the iron oxide layer is not promoted and the effect of improving wettability may be small. Therefore, the oxygen concentration is 1000 ppm by volume or more, preferably 1500 ppm by volume or more. On the other hand, if the oxygen concentration exceeds 30,000 ppm by volume, excessive iron oxide is formed, and reduction is not completed before the zinc plating process such as hot-dip galvanizing, and the remaining iron oxide may actually deteriorate the plating wettability. Therefore, the oxygen concentration is 30,000 ppm by volume or less, preferably 25,000 ppm by volume or less. The oxygen concentration is preferably 22,000 ppm by volume or less, more preferably 20,000 ppm by volume or less.

[0088] Steel plate temperature (maximum temperature reached during oxidation): 600°C or higher When oxidation treatment is performed in the oxidation step, if the steel sheet temperature (maximum temperature reached during oxidation treatment) is less than 600°C even in the above atmosphere, the amount of iron oxide formed on the surface will be small, and the effect of improving plating wettability may be small. Therefore, the steel sheet temperature (maximum temperature reached during oxidation treatment) in the oxidation step is 600°C or higher, and preferably 620°C or higher. There is no particular limit to the upper limit of the steel sheet temperature, but in order to more suitably prevent excessive oxidation of the steel sheet, which would result in unreduced iron oxide remaining in the subsequent reduction step, and to more stably obtain excellent plating properties, the upper limit is preferably 900°C or lower, and more preferably 880°C or lower. The steel sheet temperature in the oxidation step (maximum temperature reached during oxidation treatment) is preferably 860°C or lower, and more preferably 840°C or lower.

[0089] [Reduction process] A reduced iron layer is formed by heating the natural oxide film on the steel sheet surface or the iron oxide layer on the surface that is formed when oxidation is performed in the oxidation process in an iron reducing atmosphere. In the subsequent soaking process, the hydrogen concentration in the atmosphere is relatively low, so the iron reduction reaction rate is slow. Therefore, it is necessary to complete the reduction of the iron oxide in the reduction process.

[0090] Steel plate temperature (maximum temperature reached during reduction treatment): 700°C or higher If the steel sheet temperature (maximum temperature reached during reduction treatment) is less than 700°C, the reduction rate is slow and unreduced iron oxide may remain. Therefore, the steel sheet temperature in the reduction step is 700°C or higher, and preferably 750°C or higher. There is no particular upper limit to the steel sheet temperature, but it is preferably 950°C or lower from the viewpoint of reducing the load on the furnace body. The steel sheet temperature in the reduction step is preferably 920°C or lower, and more preferably 900°C or lower.

[0091] Holding time (holding time during reduction treatment): 20 seconds or more If the holding time in the reduction step (holding time during reduction treatment) is less than 20 seconds, the reduction of the iron oxide may not be completed. Therefore, the holding time in the reduction step is 20 seconds or more, and preferably 25 seconds or more. The upper limit of the retention time is not particularly limited, but from the viewpoint of productivity, it is preferably 150 seconds or less, more preferably 120 seconds or less, and even more preferably 100 seconds or less.

[0092] Hydrogen concentration (hydrogen concentration during reduction treatment): 8% by volume or more and 30% by volume or less If the hydrogen concentration in the atmosphere during the reduction step (hydrogen concentration during reduction treatment) is less than 8 volume %, unreduced iron oxide may remain. Therefore, the hydrogen concentration during the reduction step is 8 volume % or more, and preferably 10 volume % or more. On the other hand, if the hydrogen concentration exceeds 30% by volume, the reduction rate becomes saturated and the penetration of hydrogen into the steel increases excessively, which may make it difficult to sufficiently reduce the amount of hydrogen in the steel in the subsequent soaking step. Therefore, the hydrogen concentration in the reduction step is 30% by volume or less, and preferably 28% by volume or less. The hydrogen concentration is preferably 26% by volume or less, and more preferably 24% by volume or less.

[0093] The dew point of the atmosphere in the reduction step (dew point during reduction treatment) is not particularly limited, but in order to effectively prevent oxidation of the surface of the base steel sheet or the surface of the Fe-based electroplating layer and to improve the plating adhesion when a hot-dip galvanized layer is formed, it is preferably 30° C. or less, and more preferably 25° C. or less. The dew point during reduction treatment is preferably 22° C. or less, and more preferably 20° C. or less. The lower limit of the dew point is not particularly limited, but from the viewpoint of industrial controllability, it is preferably −50° C. or higher, and more preferably −45° C. or higher. The dew point during reduction treatment is preferably −40° C. or higher, and more preferably −35° C. or higher.

[0094] [Soaking process] In the soaking step, annealing is carried out to obtain the structure of the galvanized steel sheet of the present invention, and the hydrogen that has entered the steel in the reduction step is reduced.

[0095] Steel plate temperature (annealing temperature): 750℃ or higher If the steel sheet temperature (annealing temperature) in the soaking step is less than 750°C, the steel sheet surface may be reoxidized. In addition, unrecrystallized ferrite may remain or austenite may not be sufficiently generated during annealing, which may result in failure to obtain the structure required for the steel sheet of the present invention. Therefore, the steel sheet temperature is 750°C or higher, and preferably 760°C or higher. On the other hand, the upper limit of the steel sheet temperature in the soaking step is not particularly limited, but from the viewpoint of reducing the load on the furnace body and preventing excessive coarsening of austenite grains, it is preferably 950° C. or less. The annealing temperature is preferably 930° C. or less, more preferably 910° C. or less.

[0096] Holding time (holding time during soaking): 20s to 300s If the holding time in the soaking step is less than 20 seconds, hydrogen in the steel may not be sufficiently reduced. Also, the formation of austenite may be insufficient, and the steel sheet structure of the present invention may not be obtained. Therefore, the holding time is 20 seconds or more, and preferably 50 seconds or more. On the other hand, if the holding time exceeds 300 s, coarsening of austenite grains and decarburization of the surface layer may occur, and the steel sheet structure of the present invention may not be obtained. Therefore, the holding time is 300 s or less, preferably 200 s or less. The holding time is preferably 180 s or less, more preferably 160 s or less.

[0097] Hydrogen concentration (hydrogen concentration during soaking): 0.2% by volume or more and 8% by volume or less Since the reduction of iron oxide is completed in the reduction process, the hydrogen concentration in the soaking process is set to a low level within a range in which the reduced iron is not reoxidized, thereby reducing the amount of hydrogen that has entered the steel in the reduction process. If the hydrogen concentration exceeds 8% by volume, the hydrogen in the steel cannot be sufficiently reduced, and the steel sheet of the present invention cannot be obtained. Therefore, the hydrogen concentration is 8% by volume or less, and preferably 5% by volume or less. On the other hand, if the hydrogen concentration is less than 0.2% by volume, there is a risk of reoxidation of the reduced iron. Therefore, the hydrogen concentration in the soaking atmosphere is 0.2% by volume or more, and preferably 0.5% by volume or more. The hydrogen concentration is preferably 0.8% by volume or more, and more preferably 1.0% by volume or more.

[0098] Dew point of the soaking atmosphere (annealing atmosphere) during the soaking process (dew point during soaking): -30°C or higher (optimal conditions) In one embodiment of the present invention, the dew point of the atmosphere in the soaking step is preferably -30°C. By performing soaking treatment with the dew point of the atmosphere in the soaking step being -30°C or higher, the decarburization reaction is promoted and the soft surface layer can be formed deeper. The dew point of the atmosphere in the soaking step is more preferably -15°C or higher, and even more preferably -5°C or higher. There is no particular upper limit for the dew point of the atmosphere in the soaking step, but in order to suitably prevent oxidation of the base steel sheet surface or the Fe-based electroplating layer surface and to improve the plating adhesion when a hot-dip galvanized layer is provided, it is preferably 30°C or lower, more preferably 25°C or lower. Even more preferably, it is 20°C or lower.

[0099] [First cooling process] The steel sheet after the soaking step is cooled, for example, to a temperature at which it can be immersed in hot-dip galvanizing. The cooling conditions are not necessarily limited, but it is preferable to perform the cooling under the following conditions.

[0100] Hydrogen concentration (hydrogen concentration during first cooling process): 0.5% by volume or more and 30% by volume or less, dew point (dew point during first cooling process): 0°C or less (optimal conditions) Reoxidation during cooling can be suppressed by setting the hydrogen concentration in the cooling atmosphere in the first cooling step to 0.5% by volume or more and 30% by volume or less and the dew point to 0° C. or less. More preferably, the hydrogen concentration is 1.0% by volume or more and the dew point is −20° C. or less. The hydrogen concentration is preferably 1.5% by volume or more, and more preferably 2.0% by volume or more. The dew point is preferably -25°C or lower, and more preferably -30°C or lower. In addition, the lower limit of the dew point is not particularly limited, but the dew point is preferably −55° C. or higher, and more preferably −50° C. or higher. On the other hand, by setting the hydrogen concentration to 30% by volume or less, it is possible to suppress an increase in hydrogen in the steel due to hydrogen penetration during the cooling process. The hydrogen concentration is more preferably 20% by volume or less, and further preferably 10% by volume or less.

[0101] From a steel plate temperature of 600-900°C (steel plate temperature during the first cooling process), cool to 150-500°C at an average cooling rate (average cooling rate during the first cooling process): 20°C / s or less (optimal conditions) In order to more effectively prevent an increase in the amount of hydrogen in the steel during cooling, it is preferable to cool the steel sheet from a temperature of 600° C. to 900° C. at an average cooling rate of 20° C. / s or less. The average cooling rate is preferably 10° C. / s or more. Furthermore, since it is necessary to cool the steel sheet temperature in the subsequent galvanizing process to the same temperature as the galvanizing bath temperature, the cooling stop temperature (cooling stop temperature during the first cooling period) is 500°C or lower. Also, if the cooling stop temperature is less than 150°C, excessive martensitic transformation occurs before the galvanizing process, and this is tempered after the galvanizing process, which may result in insufficient strength of the final structure, so the cooling stop temperature is 150°C or higher. Here, the average cooling rate (°C / s) is obtained by (steel plate temperature (600 to 900°C)-cooling stop temperature (150 to 500°C)) / cooling time (s) from the start of cooling to the end of cooling.

[0102] [Zinc plating process] A zinc coating layer is formed on the surface of the steel sheet after the first cooling process. A typical method is to immerse the steel sheet in a hot-dip galvanizing bath. In the following, immersion in a hot-dip galvanizing bath will be described as an example.

[0103] The conditions for immersion in the hot-dip galvanizing bath are not particularly limited, and may be performed by a general method. The hot-dip galvanizing bath is composed of Al, Zn, and inevitable impurities, and the composition is not particularly specified. In one example, the Al concentration in the bath may be 0.05 mass% or more and 0.190 mass% or less. If the Al concentration in the bath is 0.05 mass% or more, the occurrence of bottom dross can be more suitably prevented. If the Al concentration in the bath is 0.190 mass% or less, the occurrence of top dross can be more suitably prevented. From the viewpoint of cost, it is preferable to set the Al concentration in the bath to 0.190 mass% or less. The plating bath temperature is not particularly specified, but may be 440°C or more and 500°C or less. The zinc plating applied in the present invention is not limited to the hot-dip galvanizing described above, and may be other methods such as electrogalvanizing or electrogalvanizing, as long as the desired steel sheet temperature is satisfied in the steps before and after the hot-dip galvanizing.

[0104] The plating weight per side is not particularly limited, but in one example, it is 25 g / m 2 More than 120g / m 2 The plating weight per side is 25g / m 2 If the thickness is 120 g / m or more, the corrosion resistance is particularly good and the coating weight is particularly easy to control. 2 The coating adhesion is particularly good if the coating weight is below 100%. The method for adjusting the coating weight is not particularly limited, but as an example in the case of hot-dip galvanizing, gas wiping is used and the coating weight can be adjusted by adjusting the gas pressure and the distance between the wiping nozzle and the steel sheet.

[0105] In the galvanizing process, after forming a galvanized layer, an alloying process may be performed to obtain a galvannealed steel sheet. By forming the galvanized layer into an alloyed galvanized layer, it is possible to further promote the desorption of hydrogen from the steel in the subsequent reheating process. The conditions of the alloying process are not particularly limited as long as a desired degree of alloying is obtained. For example, in the alloying process in hot dip galvanizing, it is preferable to hold the steel sheet at a predetermined temperature for a predetermined time. For example, the steel sheet temperature can be 440°C or higher. The steel sheet temperature can be 600°C or lower. The holding time can be 5s or more. The holding time can be 60s or less.

[0106] When alloying treatment is performed, the Fe content (degree of alloying) in the plating layer is preferably 7% by mass or more. In addition, this Fe content (degree of alloying) is preferably 15% by mass or less. By setting the degree of alloying to 7% by mass or more, no η-Zn phase remains in the alloyed galvanized layer, and hydrogen in the steel can be more suitably reduced in the reheating step. In addition, if the degree of alloying exceeds 15% by mass, the formation of Γ phase at the interface between the alloyed galvanized layer and the base steel sheet may be promoted, resulting in a decrease in plating adhesion, so that the degree of alloying is preferably 15% by mass or less.

[0107] [Second cooling process] The steel sheet after the above-mentioned galvanizing step is cooled to a cooling stop temperature of 100 to 300° C. The cooling method is not particularly limited as long as it satisfies the following cooling conditions, and may be, for example, N2 gas cooling, water cooling, or a combination thereof.

[0108] Cooling stop temperature (cooling stop temperature during the second cooling process): 100°C to 300°C In the second cooling step, untransformed austenite is cooled to a temperature range lower than the Ms point to generate martensite. Compared to austenite with an FCC crystal structure, the hydrogen diffusion rate is faster in martensite with a BCT crystal structure, so that hydrogen reduction in the subsequent reheating step can be promoted. As described above, the steel plate of the present invention needs to be controlled so that 70% or more of the total martensite contained in the structure is tempered martensite having carbides of a predetermined size, and this cannot be satisfied if the cooling stop temperature is more than 300°C. Therefore, the cooling stop temperature is 300°C or less, preferably 280°C or less. In addition, if the cooling stop temperature is less than 100°C, almost all austenite is transformed into martensite at this point, and there are cases where almost no untransformed austenite remains in the final structure, resulting in impaired ductility. In addition, there are also cases where the desired strength cannot be obtained. Therefore, the cooling stop temperature is set to 100°C or higher, and preferably 120°C or higher.

[0109] Average cooling rate from the temperature range of 350 to 450°C to (Ms point - 100°C) (average cooling rate during the second cooling process): 20°C / s or less In the second cooling step, it is preferable to cool the steel so that the steel remains in a temperature range of Ms or less and above the cooling stop temperature for a predetermined time. This allows the martensite formed just below the Ms point to be self-tempered during cooling, and the formation of carbides in the martensite required for the present invention to be further promoted. If the average cooling rate exceeds 20°C / s, the self-tempering may be insufficient and the carbides may not be obtained sufficiently. Therefore, the average cooling rate is 20° C. / s or less, preferably 10° C. / s or less, and more preferably 5° C. / s or less. Although there is no particular lower limit to the average cooling rate, a rate of 1° C. / s or more is preferable in order to more stably prevent the carbide size (average grain size of carbides contained in tempered martensite) from exceeding 200 nm due to excessively slow cooling. Here, the average cooling rate (°C / s) is obtained from "(cooling start temperature (350 to 450°C)) - (Ms point - 100°C)) / cooling time (s) from the start of cooling to (Ms point - 100°C)".

[0110] Stay in the temperature range of 100 to 350°C for 5 seconds or more Furthermore, if the residence time in the temperature range of 100 to 350° C. is less than 5 seconds in the second cooling step, self-tempering may be insufficient and the carbides may not be sufficiently generated. Therefore, the residence time is 5 seconds or more, preferably 10 seconds or more, and more preferably 15 seconds or more. The upper limit of the residence time is not particularly limited, but is preferably 60 seconds or less from the viewpoint of more stably preventing the carbide size from exceeding 200 nm.

[0111] The Ms point is the martensitic transformation start temperature and can be calculated by the following formula. Ms(℃)=539-423×{[C mass%]×100 / (100-[α area%])}-30×[Mn mass%]-12×[Cr mass%]-18×[Ni mass%]-8×[Mo mass%] In the above formula, [M mass %] (M: element) is the amount of each element contained in the steel sheet, and [α area %] is the ferrite area ratio (%) in the steel sheet structure after annealing.

[0112] [Reheating process] In this step, the steel sheet from the second cooling step is reheated to temper the martensite necessary for obtaining the steel sheet of the present invention, and at the same time, diffusible hydrogen is reduced.

[0113] In the reheating step, since a zinc-coated layer is already present on the surface of the steel sheet, there is no need to consider iron reoxidation as in the soaking step, and the reheating step can be performed in an atmosphere with a low hydrogen concentration, for example, in the air. On the other hand, if the hydrogen concentration is excessively high, the diffusible hydrogen remaining in the steel will not be reduced, and if the hydrogen concentration is excessively high, there is a risk that it will actually increase again. Therefore, although there are no particular limitations, it is preferable that the hydrogen concentration in the reheating step be 0.2 volume % or less.

[0114] Reheating temperature: Cooling stop temperature (cooling stop temperature during the second cooling process) to 450°C If the reheating temperature is lower than the cooling stop temperature (cooling stop temperature during the second cooling treatment), the tempering of the martensite is insufficient, and the carbides and tempered martensite required for the present invention cannot be obtained. In addition, if the cooling stop temperature is lower than the cooling stop temperature (cooling stop temperature during the second cooling treatment), the effect of reducing diffusible hydrogen in the steel is also insufficient. Therefore, the reheating temperature is equal to or higher than the cooling stop temperature (cooling stop temperature during the second cooling treatment), and is preferably equal to or higher than 120°C. On the other hand, if the reheating temperature exceeds 450°C, excessive tempering leads to a decrease in tensile strength and coarsening of carbides, and the steel sheet of the present invention cannot be obtained. In addition, if the temperature exceeds 450°C, the appearance of the galvanized coating may be impaired. Therefore, the reheating temperature is equal to or lower than 450°C, and is preferably equal to or lower than 430°C.

[0115] Holding time (holding time during reheating): 5 to 600 seconds If the holding time is less than 5 seconds, the tempering of the martensite is insufficient, the carbides and tempered martensite required for the present invention are not obtained, and the diffusible hydrogen in the steel is not sufficiently reduced. Therefore, the holding time is 5 seconds or more, preferably 10 seconds or more. The holding time is more preferably 15 seconds or more, more preferably 20 seconds or more. On the other hand, if the holding time exceeds 600 s, not only will the production efficiency decrease, but excessive tempering will cause a decrease in tensile strength and coarsening of carbides, and the steel sheet of the present invention may not be obtained. Therefore, the holding time is 600 s or less, preferably 500 s or less. The holding time is more preferably 400 s or less, more preferably 300 s or less.

[0116] The production conditions other than those mentioned above can be the same as those in the ordinary methods.

[0117] The thickness of the galvanized steel sheet of the present invention is not particularly limited, but is preferably 0.4 mm or more, and more preferably 0.6 mm or more. The thickness is preferably more than 0.8 mm. The thickness is more preferably 0.9 mm or more. The thickness is further preferably 1.0 mm or more. The thickness is further more preferably 1.2 mm or more. The plate thickness is preferably 3.2 mm or less, and more preferably 3.0 mm or less.

[0118] <Materials> Next, a member according to one embodiment of the present invention will be described. A member according to one embodiment of the present invention is a member made of the above-mentioned galvanized steel sheet (as a raw material). For example, the raw material galvanized steel sheet is subjected to at least one of forming and joining to form a member. Here, the above-mentioned galvanized steel sheet has a high yield ratio (YR), excellent bendability and stretch flangeability, excellent hydrogen embrittlement resistance, and a tensile strength (TS) of 780 MPa or more and less than 1180 MPa. Therefore, a member according to one embodiment of the present invention has a high yield ratio (YR), excellent bendability and stretch flangeability, excellent hydrogen embrittlement resistance, and a tensile strength (TS) of 780 MPa or more and less than 1180 MPa. Therefore, a member according to one embodiment of the present invention is particularly suitable as a member used in the automotive field.

[0119] <Method of manufacturing components> Next, a method for manufacturing a member according to one embodiment of the present invention will be described. A method for manufacturing a component according to one embodiment of the present invention includes a step of subjecting the above-mentioned zinc-plated steel sheet (e.g., a zinc-plated steel sheet manufactured by the above-mentioned method for manufacturing a zinc-plated steel sheet) to at least one of forming and joining to form a component. Here, the molding method is not particularly limited, and for example, a general processing method such as press processing can be used. The joining method is also not particularly limited, and for example, general welding such as spot welding, laser welding, and arc welding, rivet joining, crimp joining, etc. The molding conditions and joining conditions are not particularly limited, and may be in accordance with ordinary methods. EXAMPLES

[0120] The present invention will be specifically described with reference to examples, but the scope of the present invention is not limited to the following examples.

[0121] <Example 1> Using steel having the chemical composition shown in Table 1, cold-rolled steel sheets with a thickness of 1.4 mm or hot-rolled steel sheets with a thickness of 1.8 mm were produced under each of the conditions shown in Table 2, and galvanized steel sheets (hot-dip galvanized steel sheets) were produced and evaluated as follows. For all steel sheets, in the hot rolling process, the slab heating temperature was 1250° C., the finish rolling end temperature was 900° C., and the coiling temperature was 520° C. The reheating treatment in the reheating process was carried out in air. The evaluation results are shown in Table 3. The zinc plating and alloying treatment in the zinc plating process were performed under the following conditions. All of the following evaluations were performed within 72 hours after the steel sheet first reached room temperature (40°C or lower) after the reheating process specified in the present invention. Plating bath composition: Zn bath containing 0.13% Al by mass Plating bath temperature: 460℃ Plating coverage range: 30~60g / m -2 ·Alloying temperature: 450~560℃ Alloying range: 8.0-14.0% by mass

[0122] [Table 1]

[0123] [Table 2]

[0124] <Tensile test> From the obtained zinc-coated steel sheet, JIS No. 5 tensile test pieces (JIS Z2201) were taken in the direction perpendicular to the rolling direction, and the strain rate was increased to 10 -3 Tensile tests were conducted in accordance with the JIS Z2241 (2011) standard, which specifies a yield strength (YS), tensile strength (TS), elongation (EL), and yield ratio (YR=YS / TS) were determined. Examples of the present invention were those with a TS of 780 MPa or more and less than 1180 MPa and a YR of 0.60 or more. When the product of EL and TS was 10,000 or more, the TS-EL balance was evaluated as excellent.

[0125] <Hole expansion test> To evaluate the stretch flangeability, a hole expanding test was performed according to a method conforming to JIS Z 2256. A test piece of 100 mm x 100 mm was taken from the obtained galvanized steel sheet, and a hole of 10 mm in diameter was formed in the center of the test piece by punching. The clearance during punching was 12.5%. Next, using a die with an inner diameter of 75 mm, a wrinkle suppression force of 9 ton (88.26 kN) was applied around the hole, and a conical punch with an apex angle of 60° was pressed into the hole to expand the hole, and the diameter of the hole at the time of crack generation was measured. The limit hole expanding ratio λ (%) was calculated according to the following formula. Note that those with λ of 35% or more were considered to be examples of the present invention. λ(%)={(D f -D0) / D0}×100 D f : Diameter of hole when crack occurs (mm) D0: Hole diameter before hole expansion (mm)

[0126] <Structural Observation> Test pieces for microstructure observation were taken from the obtained galvanized steel sheets, and the cross section of the sheet thickness parallel to the rolling direction was polished and then corroded with nital solution. The structure was then photographed using an SEM at a magnification of 1500x in three fields of view in the region from the surface to 1 / 8 of the sheet thickness and in the region from 1 / 8 to 3 / 8 of the sheet thickness. The area fraction of the retained austenite was determined individually by measuring the X-ray diffraction intensity, and the area fraction of the as-quenched martensite was determined by subtracting it from the area fraction of the white area (as-quenched martensite and retained austenite). The area fraction of the retained austenite was determined from the ratio of the integrated X-ray diffraction intensity of the (200), (220), and (311) planes of fcc iron to the integrated X-ray diffraction intensity of the (200), (211), and (220) planes of bcc iron in the 1 / 4 plane of the sheet thickness. The retained austenite was calculated as a volume fraction from the above measurements, but the volume fraction of the retained austenite was taken as the area fraction of the retained austenite, assuming that the retained austenite was three-dimensionally homogeneous. The area ratio of each of the constituent phases was determined from the obtained images by the above-mentioned method. The area ratio of each of the constituent phases in each region was the average value of all the images taken. In addition, an SEM was used to photograph the structure of one field of view at a magnification of 5000 times in a region of 1 / 8 to 3 / 8 of the sheet thickness of the base steel sheet, and the number and total area of ​​carbides present inside the prior austenite grains containing the martensite were obtained from the image, and the area per carbide was calculated to obtain the average grain size of the carbides. Here, the average grain size is the average value of the long axis length and the short axis length when approximated as an ellipse. Note that, for one carbide, a region formed integrally without interruption in the SEM image was counted as one carbide for measurement.

[0127] <Quantitative determination of hydrogen in steel> A test piece for hydrogen analysis measuring about 5 x 30 mm was taken from the obtained galvanized steel sheet, the surface plating layer was removed using a precision grinder, and the piece was placed in a quartz tube in which the atmosphere was replaced with Ar gas, and heated to 600°C at a heating rate of 200°C / h. The amount of hydrogen released during heating was measured using a gas chromatograph. The integrated value of the amount of hydrogen released in the temperature range from room temperature to 200°C was determined as the "amount of diffusible hydrogen," and the integrated value of the amount of hydrogen released in the temperature range from 350°C to 600°C was determined as the "amount of trapped hydrogen." Note that the specimens with a diffusible hydrogen amount of 0.45 mass ppm or less were considered to be examples of the present invention. Here, the amount of diffusible hydrogen and the amount of trapped hydrogen were measured after the production of the steel sheets was completed.

[0128] <Bending test> From the obtained galvanized steel sheet, a rectangular test piece of 35 mm x 100 mm was taken so that the direction parallel to the rolling direction was the bending test axis, and a 90 degree V-bend test was performed at various bending radii at a stroke speed of 50 mm / s, a pressing load of 10 ton, and a pressing hold time of 5 seconds. For steel sheets with a thickness of more than 1.4 mm, one side of the steel sheet was ground to 1.4 mm before the test. In order to prevent the grinding process from affecting the bending test results, the test was performed with the ground surface on the inside of the bend (valley side). After the test, the ridge of the bending apex of the test piece was observed with a 10x magnifying glass, and the minimum bending radius R (mm) at which no cracks of 0.5 mm or more were observed was divided by the sheet thickness t (mm) (t = 1.4, 1.8 mm) to obtain R / t. Note that the specimens that satisfied either (A) or (B) below were considered to be examples of the present invention. (A) TS: 780MPa or more but less than 980MPa and R / t: 4.5 or less (B) TS: 980MPa or more but less than 1180MPa and R / t: 5.0 or less

[0129] <Hydrogen embrittlement resistance evaluation> A 30mm x 100mm test piece was taken from the obtained galvanized steel sheet, a spacer with a sheet thickness of 2mm was sandwiched at both ends, and the center between the spacers was spot-welded to prepare a welded test piece. For spot welding, an inverter DC resistance spot welding machine was used, and a dome-shaped electrode made of chromium copper with a tip diameter of 6mm was used. The pressure was 380kgf, the current time was 16 cycles / 50Hz, and the holding time was 5 cycles / 50Hz. The welding current value was adjusted to form a nugget diameter according to the sheet thickness. The nugget diameter was set to 3.8mm for a sheet thickness of 1.4mm and 4.4mm for a sheet thickness of 1.8mm to satisfy the following formula (2). 3.0×t 1 / 2 < nugget diameter < 3.5×t 1 / 2 ...Equation (2) In formula (2), t is the plate thickness (mm). After leaving the nugget for 24 hours after spot welding, the spacer portion was cut off and the cross section of the nugget was observed and evaluated according to the following criteria, with ranks of 1 and 2 falling within the preferred range of the present invention. Crack Observation Results Rank No crack generation: 1 (Particularly excellent in hydrogen embrittlement resistance) Only microcracks of 100 μm or less are generated: 2 (Excellent in hydrogen embrittlement resistance) Cracks exceeding 100 μm are present: 3 (Poor in hydrogen embrittlement resistance)

[0130]

Table 3

[0131] <Example 2> Using the steel having the component composition shown in Table 1, cold-rolled steel sheets with a thickness of 1.4 mm were produced under the respective conditions shown in Table 4, and hot-dip galvanized steel sheets or alloyed hot-dip galvanized steel sheets were produced, and the same evaluations as in Example 1 were carried out, and further evaluations described below were carried out. For all steel sheets, in the hot rolling process, the slab heating temperature was 1250 °C, the finish rolling end temperature was 900 °C, and the coiling temperature was 520 °C. The reheating treatment in the reheating process was carried out in the atmosphere. In Example 2, for some steel sheets (the steel sheets with "Yes" in the pre-plating process in Table 4), compared with Example 1, after the cold rolling process and before the reduction process (before the oxidation process when the treatment in the oxidation process is carried out), a treatment of applying metal plating in the pre-plating process was carried out. The evaluation results are shown in Table 5. The zinc plating treatment and the alloying treatment in the zinc plating process were carried out in the same manner as in Example 1.

[0132]

Table 4

[0133] The tensile test, the hole expansion test, the microstructure observation, the quantification of hydrogen in the steel, the bending test, and the hydrogen embrittlement resistance evaluation were carried out in the same manner as in Example 1.

[0134] <U-bending + Adhesive bending test> The U-bending + Adhesive bending test is carried out as follows From the obtained galvanized steel sheet, a 60 mm × 30 mm test piece was taken by shearing and edge grinding. Here, the 60 mm side is parallel to the width (C) direction. The test piece was prepared by U-bending (primary bending) in the width (C) direction with the rolling (L) direction as the axis with a curvature radius / sheet thickness of 4.2. In the U-bending (primary bending), as shown in Figure 1(a), a punch B1 was pressed into the steel sheet placed on a roll A1 to obtain a test piece T1. Next, as shown in Figure 1(b), the test piece T1 placed on the lower die A2 was subjected to close bending (secondary bending) in which it was crushed by the upper die B2. In Figures 1(a) and 1(b), D1 indicates the width (C) direction and D2 indicates the rolling (L) direction.

[0135] The U-bending conditions in the U-bending + close bending test are as follows. Test method: Roll support, punch intrusion Punch tip R: 5.0mm Distance between rolls: plate thickness x 2mm Stroke speed: 10mm / min Bending direction: perpendicular to rolling (C) direction The conditions for the U-bend + close bending test are as follows: Spacer thickness: Varies in 0.5mm increments Test method: Die support, punch push Molding load: 10ton Test speed: 10mm / min Holding time: 5s Bending direction: perpendicular to rolling (C) direction

[0136] The U-bend + close bending test was performed three times, and the critical spacer thickness (ST) was evaluated when no cracks occurred in all three tests. In addition, using a Leica stereo microscope, cracks with a length of 200 μm or more at 25x magnification were judged to be cracks. ST is an index for evaluating the fracture resistance properties during a collision (the fracture resistance properties of the vertical wall in an axial crushing test). The results are also shown in Table 5.

[0137] In the following cases (A) or (B), it was evaluated that the fracture resistance characteristics during impact (the fracture resistance characteristics of the vertical wall portion in the axial crushing test) were excellent. (A) When 780 MPa ≤ TS < 980 MPa, 2.0 mm ≥ ST (B) When 980 MPa ≤ TS < 1180 MPa, 3.0 mm ≥ ST

[0138] <V-bending + orthogonal VDA bending test> The V-bending + orthogonal VDA bending test is carried out as follows. A test piece of 60 mm × 65 mm was taken from the obtained galvanized steel sheet by shearing and end face grinding. Here, the 60 mm side is parallel to the rolling (L) direction. With a curvature radius / thickness of 4.2, a 90° bending process (primary bending process) was performed in the rolling (L) direction with the width (C) direction as the axis to prepare the test piece. In the 90° bending process (primary bending process), as shown in Fig. 1(a), the punch B1 was pushed into the steel sheet placed on the die A1 with a V-groove to obtain the test piece T1. Next, as shown in Fig. 1(b), the punch B2 was pushed into the test piece T1 placed on the support roll A2 so that the bending direction was perpendicular to the rolling direction to perform orthogonal bending (secondary bending process). In Fig. 1(a) and Fig. 1(b), D1 represents the width (C) direction and D2 represents the rolling (L) direction.

[0139] The conditions for V-bending in the V-bending + orthogonal VDA bending test are as follows. Test method: Die support, punch pushing Forming load: 10 tons Test speed: 30 mm / min Holding time: 5 s Bending direction: Rolling (L) direction

[0140] The conditions for VDA bending in the V-bending + orthogonal VDA bending test are as follows. Test method: Roll support, punch pushing Roll diameter: φ30 mm Punch tip R: 0.4 mm Roll spacing: (Thickness × 2) + 0.5 mm Stroke speed: 20 mm / min Test piece size: 60mm x 60mm Bending direction: perpendicular to rolling (C) direction

[0141] The stroke at maximum load is determined in the stroke-load curve obtained when the VDA bending is performed. The average value of the stroke at maximum load when the V bending + orthogonal VDA bending test is performed three times is taken as SFmax (mm). SFmax is an index for evaluating the fracture resistance characteristics during a collision (fracture resistance characteristics of the bend ridgeline in an axial crush test). The results are also shown in Table 5. The following cases (A) and (B) were evaluated as excellent in fracture resistance characteristics during a collision (fracture resistance characteristics of the bend ridgeline in an axial crush test). (A) When 780MPa≦TS<980MPa, 29.5mm≦SFmax (B) When 980MPa≦TS<1180MPa, 28.5mm≦SFmax

[0142] <Axial Crushing Test> A test piece of 160 mm x 200 mm was taken from the obtained hot-dip galvanized steel sheet by shearing. Here, the 160 mm side is parallel to the rolling (L) direction. Using a die having a punch shoulder radius of 5.0 mm and a die shoulder radius of 5.0 mm, the hat-shaped member 10 shown in Fig. 2(a) and Fig. 2(b) was produced by forming (bending) to a depth of 40 mm. In addition, the steel plate used as the material for the hat-shaped member was separately cut into a size of 80 mm x 200 mm. Next, the cut-out steel plate 20 and the hat-shaped member 10 were spot-welded to produce a test member 30 as shown in Fig. 2(a) and Fig. 2(b). Fig. 2(a) is a front view of the test member 30 produced by spot-welding the hat-shaped member 10 and the steel plate 20. Fig. 2(b) is a perspective view of the test member 30. The position of the spot welded portion 40 was such that the end of the steel plate and the welded portion were spaced 10 mm apart, and the distance between the welded portions was 20 mm, as shown in FIG. 2(b). Next, as shown in FIG. 2(c), the test member 30 was joined to the base plate 50 by TIG welding to prepare a sample for the axial crushing test. Next, the impactor 60 was made to collide with the prepared sample for the axial crushing test at a constant speed of 10 mm / min, and the sample for the axial crushing test was crushed by 70 mm. As shown in FIG. 2(c), the crushing direction D3 was parallel to the longitudinal direction of the test member 30. The results are also shown in Table 5. Axial compression fracture (visual crack) judgment More preferable (◎): No external cracks were observed in the sample after the axial crush test. Good (○): One or less external cracks were observed on the sample after the axial crush test.

[0143] Considering the influence of plate thickness, U-bend + close bending test, V-bend + orthogonal VDA bending test, and axial crushing test of galvanized steel sheets with a plate thickness of more than 1.2 mm were all performed with steel sheets with a plate thickness of 1.2 mm. Steel sheets with a plate thickness of more than 1.2 mm were ground on one side to make the plate thickness 1.2 mm. Since grinding may affect the bendability of the steel sheet surface, the ground surface was placed on the inside of the bend (valley side) in the U-bend + close bending test, and the ground surface was placed on the outside of the bend (mountain side) in the V-bend + orthogonal VDA bending test during the V-bend test, and the ground surface was placed on the inside of the bend (valley side) during the subsequent VDA bending test. On the other hand, the U-bend + close bending test, V-bend + orthogonal VDA bending test, and axial crushing test of galvanized steel sheets with a plate thickness of 1.2 mm or less were performed without grinding because the influence of plate thickness is small.

[0144] When the nanohardness was measured at more than 300 points in a 50 μm x 50 μm area on the plate surface at a position 1 / 4 of the way through the plate thickness of the soft surface layer from the surface of the base steel plate, if the proportion of nanohardness of 7.0 GPa or higher was 0.10 or less, it became possible to further suppress the generation, connection, and crack propagation of voids in hard structures (such as martensite) and inclusions during press forming and collision, and excellent R / t and SFmax were obtained.

[0145] After the plating was removed, the steel sheet was mechanically polished from the surface to 1 / 4 of the way down to the soft surface layer at 5μm, then buffed with diamond and alumina from the surface to 1 / 4 of the way down to the soft surface layer, and then polished with colloidal silica. Load: 500μN Measurement area: 50μm x 50μm Dot spacing: 2μm A total of 512 nano-hardness points were measured under the above conditions.

[0146] When the standard deviation σ of the nanohardness of the sheet surface at a position 1 / 4 of the thickness direction depth of the soft surface layer from the surface of the base steel sheet is 1.8 GPa or less, and further, when the standard deviation σ of the nanohardness of the sheet surface at a position 1 / 2 of the thickness direction depth of the soft surface layer from the surface of the base steel sheet is 2.2 GPa or less, it becomes possible to further suppress the generation and connection of voids during press forming and collision, as well as the propagation of cracks, and excellent R / t and SFmax are obtained.

[0147] For steel sheets on which a metal plating layer had been formed after the zinc plating layer had been peeled off, mechanical polishing was performed from the surface of the base steel sheet to a position 1 / 4 of the depth in the sheet thickness direction of the soft surface layer, buff polishing with diamond and alumina, and colloidal silica polishing were performed. Using a Hysitron Tribo-950, a Berkovich-shaped diamond indenter was used. Load: 500μN Measurement area: 50μm x 50μm Dot spacing: 2μm A total of 512 nano-hardness points were measured under the above conditions.

[0148] Next, the surface soft layer was mechanically polished to a position halfway down the thickness direction, buffed with diamond and alumina, and polished with colloidal silica. Load: 500μN Measurement area: 50μm x 50μm Dot spacing: 2μm A total of 512 nano-hardness points were measured under the above conditions.

[0149] [Table 5]

[0150] From Examples 1 and 2, the galvanized steel sheets of the invention examples had a TS of 780 MPa or more and 1180 MPa or less, a YR of 0.60 or more, and diffusible hydrogen in steel of 0.45 mass ppm or less, and were excellent in stretch flangeability, bendability, and hydrogen embrittlement resistance. The steel sheets of the comparative examples were inferior in at least one of TS, YR, stretch flangeability, bendability, and hydrogen embrittlement resistance.

[0151] In Example 2, when the dew point was -15°C, the thickness of the soft surface layer was less than 17 µm, and the fracture (visual cracking) in the axial crushing test was judged to be "○". However, even when the thickness of the soft surface layer was less than 17 µm, when a metal plating layer was included, the fracture resistance characteristics were excellent and the fracture (visual cracking) in the axial crushing test was judged to be "◎".

[0152] In addition, the components obtained by forming or joining the galvanized steel sheets of the examples of the invention had a TS of 780 MPa or more and 1,180 MPa or less, a YR of 0.60 or more, and diffusible hydrogen in the steel of 0.45 mass ppm or less, and were excellent in stretch flangeability, bendability, and hydrogen embrittlement resistance. [Explanation of symbols]

[0153] 10 Hat-shaped member 20. Galvanized steel sheet 30 Test components 40 Spot welds 50 Main plate 60 Impactor A1 Die A2 Support roll B1 Punch B2 Punch D1 width (C) direction D2 Rolling (L) direction D3 Crushing direction T1 test piece [Industrial Applicability]

[0154] According to the present invention, it is possible to obtain a galvanized steel sheet which is suitable mainly for use in automobile parts and has a tensile strength TS of 780 MPa or more and less than 1,180 MPa, a yield ratio of 0.60 or more, and excellent bendability, stretch flangeability and hydrogen embrittlement resistance.

Claims

1. A galvanized steel sheet having a base steel sheet and a galvanized layer formed on the base steel sheet, The base steel sheet is In terms of area ratio, Ferrite: less than 65%; The sum of martensite and bainite: 25% or more, Retained austenite: A steel structure having 3% to 10%. In terms of area ratio, 70% or more of all martensite in the steel structure in 1 / 8 to 3 / 8 of the sheet thickness of the base steel sheet is tempered martensite having carbides with an average grain size of 50 nm or more and 200 nm or less, The tensile strength is 780 MPa or more and less than 1180 MPa, The yield ratio is 0.60 or more, A zinc-plated steel sheet, wherein the integrated amount of hydrogen released when the base steel sheet is heated from room temperature to 200°C is 0.45 mass ppm or less.

2. The steel composition of the base steel sheet is, in mass%, C: 0.080% or more and 0.300% or less, Si: 0.20% or more and 2.00% or less, Mn: 1.00% or more and 4.00% or less, P: 0.10% or less, S: 0.0200% or less, Al: 0.003% or more and 0.100% or less, N: 0.0100% or less; The galvanized steel sheet according to claim 1 , wherein the balance consists of Fe and unavoidable impurities.

3. The steel composition further comprises, in mass%, B: 0.0100% or less, Ti: 0.200% or less, Nb: 0.200% or less, Sb: 0.200% or less, Sn: 0.200% or less, V: 0.100% or less, Cu: 2.00% or less, Cr: 2.00% or less, Ni: 2.00% or less, Mo: 1.00% or less, Ta: 0.100% or less, W: 0.500% or less, Zr: 0.020% or less, Ca: 0.0200% or less, Mg: 0.0200% or less, Zn: 0.020% or less, Co: 0.020% or less, Ce: 0.0200% or less, Se: 0.0200% or less, Te: 0.0200% or less, Ge: 0.0200% or less, As: 0.0200% or less, Sr: 0.0200% or less, Cs: 0.0200% or less, Hf: 0.0200% or less, Pb: 0.0200% or less, Bi: 0.0200% or less; REM (excluding Ce): at least one selected from the following: 0.0200% or less The galvanized steel sheet according to claim 2, comprising:

4. The steel plate according to any one of claims 1 to 3, which satisfies one or more of the following (A) or (B), (C), (D), and (E). (A) When the base steel sheet has a surface layer in a region of 200 μm or less from the surface of the base steel sheet in the sheet thickness direction, The surface layer has a soft surface layer having a Vickers hardness of 85% or less of the Vickers hardness at a 1 / 4 position of the plate thickness. (B) When the base steel sheet has a surface layer in a region of 200 μm or less from the surface of the base steel sheet in the sheet thickness direction, The surface layer has a surface soft layer having a Vickers hardness of 85% or less of the Vickers hardness at a quarter of the plate thickness position, When the nano hardness was measured at 300 or more points in a 50 μm×50 μm region on the sheet surface at a 1 / 4 position and a 1 / 2 position of the sheet thickness direction depth of the soft surface layer from the surface of the base steel sheet, the ratio of the number of measurements in which the nano hardness of the sheet surface at a position of 1 / 4 of the sheet thickness direction depth of the soft surface layer from the surface of the base steel sheet is 7.0 GPa or more to the total number of measurements is 0.10 or less, Furthermore, the standard deviation σ of the nano-hardness of the sheet surface at a position of ¼ of the sheet thickness direction depth of the soft surface layer from the surface of the base steel sheet is 1.8 GPa or less, Furthermore, the standard deviation σ of the nano-hardness of the sheet surface at a position half the depth in the sheet thickness direction of the soft surface layer from the surface of the base steel sheet is 2.2 GPa or less. (C) The zinc-plated steel sheet has a metal plating layer formed between the base steel sheet and the zinc plating layer on one or both sides thereof. (D) The zinc plating layer is a zinc alloy plating layer. (E) When the base steel sheet is heated from room temperature to 600°C, the integrated amount of hydrogen released in the temperature range of 350 to 600°C is 0.05 mass ppm or more.

5. A member made using the galvanized steel sheet according to any one of claims 1 to 3.

6. A member formed using the galvanized steel sheet according to claim 4.

7. A hot rolling process in which a slab having the steel composition according to claim 2 or 3 is heated to a temperature range of 1100 to 1350 ° C., hot rolled at a finish rolling end temperature of 800 to 950 ° C., and coiled at a coiling temperature of 650 ° C. or less; A reduction process in which the steel sheet after the hot rolling process is held at 700° C. or higher in a reducing atmosphere having a hydrogen concentration of 8 vol.% or more and 30 vol.% or less for 20 s or more; a soaking step of holding the steel sheet after the reduction step in a soaking atmosphere having a hydrogen concentration of 0.2 vol% or more and 8 vol% or less at 750°C or more for 20 s to 300 s; A first cooling step of cooling the steel sheet after the soaking step; A galvanizing step of forming a galvanized layer on the surface of the steel sheet after the first cooling step; a second cooling step in which the steel sheet after the galvanizing step is cooled from a temperature range of 350 to 450 ° C. to (Ms point - 100 ° C.) at an average cooling rate of 20 ° C. / s or less and is retained in a temperature range of 100 to 350 ° C. for 5 seconds or more to a cooling stop temperature of 100 to 300 ° C.; A reheating process in which the steel sheet after the second cooling process is held in a temperature range of from the cooling stop temperature to 450 ° C. for 5 to 600 s; Including, Alternatively, there is provided a method for producing a galvanized steel sheet having a base steel sheet and a galvanized layer formed on the base steel sheet, the method further satisfying one or more selected from the following (a), (b), (c) and (d): the base steel sheet has a steel structure which, in terms of area ratio, is less than 65% ferrite, 25% or more in total of martensite and bainite, and 3% or more and 10% or less retained austenite, wherein, in terms of area ratio, 70% or more of all martensite in the steel structure at 1 / 8 to 3 / 8 of the sheet thickness of the base steel sheet is tempered martensite having carbides having an average grain size of 50 nm or more and 200 nm or less, the base steel sheet has a tensile strength of 780 MPa or more and less than 1,180 MPa, a yield ratio of 0.60 or more, and an integrated value of the amount of hydrogen released when the temperature of the base steel sheet is raised from room temperature to 200°C is 0.45 ppm by mass or less. (a) After the zinc plating step, the zinc plating layer is formed on the surface of the steel sheet, and then the steel sheet is further subjected to an alloying treatment. (b) after the hot rolling step and before the reducing step, a cold rolling step of cold rolling at a rolling reduction rate of 20% or more is included. (c) A pre-plating step is included in which metal plating is applied to one or both sides of the steel sheet after the hot rolling step and before the reducing step to form a metal plating layer. (d) An oxidation step is included in which the steel sheet after the hot rolling step and before the reducing step is heated to 600° C. or higher in an oxidizing atmosphere containing an oxygen concentration of 1,000 ppm by volume or more and 30,000 ppm by volume or less.

8. The method for producing a galvanized steel sheet according to claim 7, which satisfies one or more of the following (e), (f) and (g). (e) In the first cooling step, the steel sheet after the soaking step is cooled from 600 to 900°C to 150 to 500°C at an average cooling rate of 20°C / s or less in an atmosphere having a hydrogen concentration of 0.5 vol% or more and 30 vol% or less and a dew point of 0°C or less. (f) In the second cooling step, the average cooling rate from the temperature range of 350 to 450° C. to (Ms point −100° C.) is set to 10° C. / s or less, and the material is allowed to dwell in the temperature range of 100 to 350° C. for 10 seconds or more, and is cooled to a cooling stop temperature of 100 to 300° C. (g) The soaking atmosphere in the soaking step has a dew point of −30° C. or higher.

9. A method for manufacturing a component, comprising a step of subjecting the galvanized steel sheet according to any one of claims 1 to 3 to at least one of forming and joining to form a component.

10. A method for manufacturing a component, comprising the step of subjecting the galvanized steel sheet according to claim 4 to at least one of forming and joining to form a component.

Citation Information

Patent Citations

  • HIGH STRENGTH STEEL SHEET HAVING MAXIMUM TENSILE STRENGTH OF &gt;=900 MPa AND HAVING SATISFACTORY DUCTILITY AND DELAYED FRACTURE RESISTANCE, METHOD FOR PRODUCING HIGH STRENGTH COLD ROLLED STEEL SHEET, AND METHOD FOR PRODUCING HIGH STRENGTH GALVANIZED STEEL SHEET

    JP2011111671A

  • Methods for manufacturing galvanized steel sheet and galvannealed steel sheet

    JP2018165398A

  • Steel plate for producing press-hardened parts, press-hardened parts having a combination of high strength and crush ductility, and methods for producing the same

    JP2020523473A

  • High-strength hot-dip galvanized steel sheet and production method thereof

    WO2016113788A1

  • Method for manufacturing high-strength hot-dip galvanized steel sheet, method for manufacturing hot-rolled steel plate for high-strength hot-dip galvanized steel sheet, method for manufacturing cold-rolled steel plate for high-strength hot-dip galvanized steel sheet, and high-strength hot-dip galvanized steel sheet

    WO2017090236A1